Method for producing thermoplastic resin foamed particle molded body

By using the method of producing thermoplastic resin foamed particles molded in the crack filling method, including crack filling and in-mold forming processes, the problem of uneven compression of polypropylene resin foamed particles in the mold is solved, and the molded body is realized High toughness and short water cooling time.

CN118660797BActive Publication Date: 2025-02-25JSP CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380020648.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-17
Filing Date
2023-03-10
Publication Date
2025-02-25
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

In the crack filling method, the uneven compression of the polypropylene resin foam particles in the forming mold leads to insufficient local welding of the forming body, reducing the toughness of the forming body. At the same time, the water cooling time in the forming mold is long and difficult to shorten. .

Method used

A method for producing a thermoplastic resin foamed particle molded body is adopted, including a crack filling process and an in-mold forming process. In the crack filling step, the foamed particles with the foamed layer are filled in the forming mold, and the heating medium is supplied after the forming mold is completely closed, so that the foamed particles are welded to each other.

Benefits of technology

This method can shorten the water cooling time in the forming mold, improve the surface properties and welding properties of the forming body, and is suitable for the production of the forming body of complex shapes, and suppress the shrinkage and deformation of the forming body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118660797B_ABST
    Figure CN118660797B_ABST
Patent Text Reader

Abstract

The method for manufacturing a thermoplastic resin foamed bead molded body includes a crack filling step and an in-mold molding step. The foamed bead (2) used in the crack filling step has a columnar shape and has one or more defective parts selected from the group consisting of through holes and grooves, or both. The molding cavity (12) of the molding die (1) has a length in the opening and closing direction of the molding die (1) that is shorter than the average length L. A The first portion (121) is longer than the average length L A The short second part (122). The minimum value P1 of the compression rate of the first part (121) in the crack filling process min The maximum value P2 of the compression ratio of the second part (122) max Difference P2 max ‑P1 min It is 5% or more and 100% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a thermoplastic resin foamed particle molded body. Background Art

[0002] Polypropylene resin foamed particle molded bodies are used for various purposes such as packaging materials, containers, and cushioning materials because they are lightweight and have excellent cushioning properties and rigidity. In recent years, the use of polypropylene resin foamed particle molded bodies has been increasingly expanded, and along with this, there is a demand for forming polypropylene resin foamed particles into various shapes.

[0003] The polypropylene resin foamed bead molded body is manufactured by, for example, filling the polypropylene resin foamed beads into a forming mold and supplying a heating medium such as steam into the forming mold for heating. In the in-mold forming method, if a heating medium is supplied into the forming mold, the foamed beads are foamed for a second time, and their surfaces melt. As a result, the foamed beads in the forming mold are mutually welded, and a molded body having a shape corresponding to the shape of the cavity of the forming mold can be obtained. The molded body just after being formed is easy to expand due to the secondary foaming, so it is demolded from the forming mold after cooling with water, air, etc. in the forming mold.

[0004] In the in-mold forming method, when the foaming particles are not filled into the forming mold sufficiently, the appearance of the obtained molded body is easy to deteriorate. Therefore, as a method for filling the polypropylene resin foaming particles into the forming mold as tightly as possible, there is a method called crack filling (for example, refer to patent document 1). In the crack filling, the forming mold is not completely clamped, but after the foaming particles are filled into the cavity in a state where the movable mold is slightly retreated from the fixed mold to the mold opening direction, the forming mold is clamped, thereby mechanically compressing the foaming particles in the cavity. Crack filling does not require special equipment, so it is a method generally adopted in the in-mold forming method.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2020 / 189389 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, during crack filling, the foamed beads are compressed in one direction due to the clamping of the forming mold, so the difference in the amount of compression of the foamed beads tends to become locally large depending on the shape of the desired molded body. Therefore, when it is desired to produce a molded body having a complicated shape, such as a molded body having a thick wall portion thicker than the average thickness of the molded body and a thin wall portion thinner than the average thickness of the molded body, it is easy to form a part in the molded body where the foamed beads are not fully fused to each other, which may lead to a potential reduction in the toughness of the molded body.

[0010] In addition, with the recent increase in environmental awareness, it is desired to reduce energy consumption in the manufacturing process of molded products. From this point of view, it is desired to further shorten the water cooling time in the mold. In particular, in molded products such as molded products with large thickness of thick wall parts and molded products with large difference in thickness between thick wall parts and thin wall parts, the water cooling time in the mold tends to be long.

[0011] The present invention has been made in view of the above background, and its object is to provide a method for producing a thermoplastic resin foamed particle molded body, which can shorten the water cooling time in the molding die and can mold a molded body having excellent surface properties and weldability and having a complex shape.

[0012] One aspect of the present invention is a method for producing a thermoplastic resin foamed bead molded article according to the following [1] to

[11] .

[0013] [1] A method for producing a thermoplastic resin foamed particle molded body, wherein:

[0014] The method for producing the thermoplastic resin foamed particle molded body comprises:

[0015] a crack filling step of filling the molding cavity of the molding die with the crack gap opened with thermoplastic resin foamed particles having a foam layer, and then completely closing the molding die; and

[0016] In the in-mold forming step, after the crack filling step is completed, a heating medium is supplied into the forming cavity to fuse the foamed particles to each other.

[0017] When the forming mold is completely closed, the forming cavity has a first portion and a second portion, and the length of the first portion in the opening and closing direction of the forming mold is greater than the average length L represented by the following formula (1): A The length of the second portion in the opening and closing direction of the forming mold is longer than the average length L A short,

[0018] The minimum value P1 of the compression rate of the first portion represented by the following formula (2) in the crack filling step is: minThe maximum value P2 of the compression rate of the second part expressed by the following equation (3) max Difference P2 max -P1 min is 5% or more and 100% or less,

[0019] The average length L of the forming cavity in the opening and closing direction A More than 10mm,

[0020] The foamed bead has a columnar shape and has one or more defective parts selected from the group consisting of a through hole that axially penetrates the inside of the foamed bead and a groove that extends axially on the side circumference of the foamed bead.

[0021] The ratio Ca / A of the average cross-sectional area Ca of each defect to the average cross-sectional area A of the foamed beads in the cross-sectional surface obtained by cutting the foamed beads at the center of the axial direction with a plane perpendicular to the axial direction is 0.01 or more and 0.20 or less, and the ratio Ct / A of the total cross-sectional area Ct of the defects to the average cross-sectional area A of the foamed beads is 0.02 or more and 0.20 or less,

[0022] L A =V / S···(1)

[0023] P1 min =(δ / L1 max )×100···(2)

[0024] P2 max =(δ / L2 min )×100···(3)

[0025] Wherein, V in the formula (1) is the volume of the molding cavity when the molding die is completely closed (unit: mm 3 ), S is the projection area of ​​the forming cavity when projecting the forming cavity in the opening and closing direction of the forming mold (unit: mm 2 ), δ in the above formula (2) and formula (3) is the size of the gap in the gap filling process (unit: mm), L1 in the above formula (2) max is the maximum value (unit: mm) of the length of the first portion in the opening and closing direction measured when the forming mold is completely closed, and L2 in the formula (3) min It is the minimum value (unit: mm) of the length of the second portion in the opening and closing direction measured in a state where the forming mold is completely closed.

[0026] [2] The method for producing a thermoplastic resin foamed bead molded article according to [1], wherein a ratio of the apparent density of the foamed beads to the bulk density of the foamed beads is greater than 1.6 and less than 2.0.

[0027] [3] The method for producing a thermoplastic resin foamed particle molded article according to [1] or [2], wherein the maximum value P2 of the compressibility of the second portion in the crack filling step is max It is 25% or more and 150% or less.

[0028] [4] The method for producing a thermoplastic resin foamed particle molded article according to any one of [1] to [3], wherein the maximum value L1 of the length of the first portion in the opening and closing direction of the molding die is max More than 55mm.

[0029] [5] The method for producing a thermoplastic resin foamed bead molded body according to any one of [1] to [4], wherein the fusion rate of the portion of the thermoplastic resin foamed bead molded body obtained by the production method corresponding to the first portion is 70% or more.

[0030] [6] The method for producing a thermoplastic resin foamed bead molded article according to any one of [1] to [5], wherein the porosity of the thermoplastic resin foamed bead molded article obtained by the production method is 4% or more and 12% or less.

[0031] [7] The method for producing a thermoplastic resin foamed bead molded article according to any one of [1] to [6], wherein the foamed beads have one or more through holes as the defective portion.

[0032] [8] A method for producing a thermoplastic resin foamed particle molded body according to any one of [1] to [7], wherein the foamed particles have a foaming layer and a weldability improving layer covering the foaming layer, the base resin of the foaming layer is a first thermoplastic resin, and the base resin of the weldability improving layer is a second thermoplastic resin.

[0033] [9] The method for producing a thermoplastic resin foamed bead molded article according to any one of [1] to [8], wherein the thermoplastic resin constituting the foamed layer is a polyolefin-based resin.

[0034]

[10] The method for producing a thermoplastic resin foamed particle molded body according to any one of [1] to [9], wherein the thermoplastic resin constituting the foamed layer is an ethylene-propylene random copolymer having an ethylene component content of 0.5% by mass or more and 3.5% by mass or less.

[0035]

[11] The method for producing a thermoplastic resin foamed bead molded article according to any one of [1] to

[10] , wherein the bulk density of the foamed beads is 10 kg / m 3 Above and 50kg / m 3 the following.

[0036] Effects of the Invention

[0037] According to the above aspect, it is possible to provide a method for producing a thermoplastic resin foamed bead molded article, which can shorten the water cooling time in the molding die and can mold an article having a complex shape and excellent surface properties and weldability. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a cross-sectional view of a main part of the forming mold showing a state in which the foamed beads are filled in the crack filling step.

[0039] Figure 2 This is a cross-sectional view of a main part of the forming mold showing a state in which the filling of the foamed beads is completed in the crack filling step.

[0040] Figure 3 It is a cross-sectional view of a main part of the forming mold showing a completely closed state in the crack filling step.

[0041] Figure 4 It is a partial enlarged view of the main part of the forming mold showing a fully closed state.

[0042] Figure 5 This is a schematic diagram of the appearance of a foamed bead having a through hole as a defective portion.

[0043] Figure 6 yes Figure 5 Cross-sectional view taken along line VI-VI (top view of the cut surface of the foamed particles).

[0044] Figure 7 This is a schematic diagram showing the appearance of a foamed bead having a groove as a defective portion.

[0045] Figure 8 yes Figure 7 Cross-sectional view taken along line VIII-VIII (top view of the cut surface of the foamed particles).

[0046] Fig. 9 This is a schematic diagram showing the appearance of expanded beads having a weldability-improving layer.

[0047] Fig.10 yes Fig. 9 XX line cross-sectional view (top view of the cut surface of the foamed particles).

[0048] Fig.11It is an explanatory diagram showing a method of calculating the area of ​​the high temperature peak. DETAILED DESCRIPTION

[0049] (Method for producing thermoplastic resin foamed particle molded article)

[0050] When manufacturing the thermoplastic resin foamed bead molded body (hereinafter referred to as "foamed bead molded body" or "molded body"), first, a crack filling step is performed, in which thermoplastic resin foamed beads (hereinafter referred to as "foamed beads") having a foam layer are filled into the molding cavity of the molding die in a state where the crack gap is opened, and then the molding die is completely closed. For example, Figure 1 As shown, the forming mold 1 for manufacturing the formed body has a fixed mold 11 and a movable mold 13, the movable mold 13 is configured to form a forming cavity 12 between the fixed mold 11, and the movable mold 13 is configured to be able to reciprocate in one direction relative to the fixed mold 11. In addition, hereinafter, the moving direction of the movable mold is sometimes referred to as the "opening and closing direction".

[0051] The molding cavity provided in the molding die has a shape corresponding to the shape of the desired molding. When the length of the molding in the opening and closing direction of the molding die is set to the thickness of the molding, the molding to be obtained by the manufacturing method has a thick-walled portion thicker than the average thickness of the molding and a thin-walled portion thinner than the average thickness of the molding. Such a molding is also referred to as a molding having a thick-thickness. Therefore, the molding cavity 12 has a first portion 121 and a second portion 122, and when the molding die 1 is completely closed, the length of the first portion 121 in the opening and closing direction is longer than the average length L represented by the following formula (1): A The length of the second portion 122 in the opening and closing direction is longer than the average length L A short.

[0052] L A =V / S···(1)

[0053] Wherein, V in the formula (1) is the volume of the molding cavity when the molding die is completely closed (unit: mm 3 ), S is the projection area of ​​the forming cavity when projecting the forming cavity in the opening and closing direction of the forming mold (unit: mm 2 ).

[0054] In addition, the average length L of the molding cavity in the opening and closing direction is A The detailed structure of the molding cavity will be described later.

[0055] The foamed particles filled in the forming mold have a columnar shape and have one or more defective parts selected from a group consisting of a through hole that penetrates the inside of the foamed particles in the axial direction and a groove that extends in the axial direction on the side circumference of the foamed particles. In addition, the ratio Ca / A of the average cross-sectional area Ca of each of the defective parts to the average cross-sectional area A of the foamed particles in the cut surface obtained by cutting the foamed particles in the center of the axial direction with a plane perpendicular to the axial direction is greater than 0.01 and less than 0.20, and the ratio Ct / A of the total cross-sectional area Ct of the defective parts to the average cross-sectional area A of the foamed particles is greater than 0.02 and less than 0.20. By providing the foamed particles with the above-mentioned structure, even when a molded body with a complex shape is molded by the crack filling method, a good molded body can be easily manufactured. In addition, the detailed structure of the foamed particles will be described later.

[0056] In the crack filling step, the foamed particles are filled into the forming mold, for example, in the following manner. Figure 1 As shown in FIG. 1 , the movable mold 13 is arranged at a position where the molding cavity 12 is formed and is separated from the fixed mold 11 in the opening and closing direction, and a crack gap is formed between the movable mold 13 and the fixed mold 11. At this time, the crack gap is formed so that the foamed particles 2 do not leak out of the molding cavity 12. Then, the molding cavity 12 is filled with the foamed particles 2 in a state where the molding cavity 12 is not completely closed. When the foamed particles 2 are filled into the molding cavity 12, for example, Figure 2 As shown, the foamed beads 2 are not compressed by the forming die 1 and maintain their natural shape.

[0057] During the crack filling process, Figure 1 The size of the slit gap δ (unit: mm) shown is set to the minimum value P1 of the compression rate in the first portion 121 expressed by the following formula (2): min The maximum value P2 of the compression ratio in the second part 122 expressed by the following equation (3) max Difference P2 max -P1 min It is 5% or more and 100% or less.

[0058] P1 min =(δ / L1 max )×100···(2)

[0059] P2 max =(δ / L2 min )×100···(3)

[0060] Wherein, L1 in the formula (2) maxis the maximum value (unit: mm) of the length of the first portion in the opening and closing direction measured when the forming mold is completely closed, and L2 in the formula (3) min It is the minimum value (unit: mm) of the length of the second portion in the opening and closing direction measured in a state where the forming mold is completely closed.

[0061] like Figure 2 As shown, after the foaming particles 2 are filled into the forming cavity 12, the movable mold 13 is moved toward the fixed mold 11 to close the forming mold 1. When the forming mold 1 is completely closed, the foaming particles 2 in the forming cavity 12 are mechanically compressed by the movable mold 13 in the opening and closing direction (refer to Figure 3 ).

[0062] After the crack filling process is performed as described above, an in-mold forming process is performed, in which a heating medium such as steam is supplied into the forming cavity to fuse the foamed particles to each other. In the in-mold forming process, the foamed particles in the forming mold are heated by the heating medium, undergo secondary foaming, and fuse to each other. Thus, the foamed particles in the forming mold can be integrated to form a molded body.

[0063] After the foamed beads are heated, the molded body in the mold is cooled with water or the like to stabilize its shape. Then, the molded body is removed from the mold to complete the in-mold molding.

[0064] In the manufacturing method, in order to obtain a molded body having a thick thickness, the minimum value P1 of the compression rate of the first part of the molding cavity when the foamed beads are filled with cracks is set to min The maximum compression ratio of the second part P2 max Difference P2 max -P1 min The difference in compression ratio P2 is set to be 5% or more and 100% or less. max -P1 min It is controlled by the shape of the forming cavity and the size δ of the crack gap. Here, the foamed particles having the specific shape are filled into the forming cavity having the above-mentioned structure. By using a heating medium to perform in-mold forming after the crack filling in this way, the water cooling time of the molded body in the forming mold can be easily shortened. Furthermore, the molded body obtained in this way has excellent surface properties and weldability even in the case of a complex shape with thick and thin thickness. Furthermore, in the manufacturing method, when the molded body after demolding from the forming mold is not subjected to a curing process, significant shrinkage and deformation of the molded body can be suppressed. As reasons for obtaining such an effect, for example, the following reasons can be considered.

[0065] As described above, the foamed particles have one or more defective parts selected from the group consisting of grooves and through holes. It is believed that if such foamed particles are used to perform crack filling in the above-mentioned manner, then when the forming mold is completely closed, the defective parts of the foamed particles such as through holes and grooves, the gaps between the foamed particles, etc. are intricately connected, thereby forming a fine passage through which the heating medium can pass in the forming cavity. Therefore, it is believed that when a heating medium such as steam is supplied to the forming mold, the heating medium can easily reach the inside of the forming mold through the fine passage, and the entire foamed particles in the forming mold can be easily heated. In addition, it is believed that the foamed particles having the defective parts have moderate secondary foaming properties, and therefore expand moderately when heated by the heating medium. As a result, it is believed that by using the foamed particles, even if the difference in compression rate P2 max -P1 min Under the condition that the temperature is relatively large within the above range, the weldability is also excellent, and a molded body with good appearance can be obtained. In addition, it is believed that even under the condition that the molding temperature during in-mold molding is low, the weldability is also excellent, and a molded body with good appearance can be obtained.

[0066] In addition, the foamed particles with the defective portion have moderate secondary foaming properties, so even when the internal pressure is not applied in advance or the applied internal pressure is relatively low, secondary foaming can be fully performed in the forming mold. Furthermore, it is believed that since the foamed particles have the above-mentioned defective portion, excessive expansion of the molded body at the time when the heating with the heating medium is completed can be avoided. As a result, the time required from the completion of the heating of the foamed particles to the stabilization of the shape of the molded body in the forming mold can be shortened. As a result, the time required for cooling the molded body in the forming mold can be shortened.

[0067] Furthermore, a moderate open-cell structure is formed in the molded body after the mold forming is completed. The open-cell structure is a tiny space portion that is connected to the outside of the molded body. The open-cell structure is formed by the gaps between the foamed particles being connected, the continuous bubble portions of the foamed particles constituting the molded body, and the defective portions being complexly connected. In this way, it is believed that when the molded body with the open-cell structure is taken out from the forming mold, air quickly flows into the bubbles inside the molded body via the open-cell structure, and as a result, the internal pressure of the molded body is stabilized at an early stage. Therefore, it is believed that according to the manufacturing method, even without performing a curing process, significant shrinkage and deformation of the molded body can be suppressed.

[0068] When using foamed beads without defects, the difference in compression rate P2 max -P1 minWhen the cracks are filled under the above-mentioned conditions and then molded, there is a risk of poor welding of the foamed particles and reduced toughness of the molded body. In addition, there is a risk of excessively long water cooling time of the molded body in the molding die.

[0069] In addition, even in the case of defective parts, when the ratio Ca / A of the average cross-sectional area Ca of each defective part to the average cross-sectional area A of the foamed particles and / or the ratio Ct / A of the total cross-sectional area Ct of the defective parts to the average cross-sectional area A of the foamed particles is too small, it is difficult to obtain the effect brought by the defective parts. Therefore, there is a risk of poor welding between the foamed particles and reduced toughness of the molded body. In addition, there is a risk that the water cooling time of the molded body in the molding die becomes too long. In addition, if the curing process is not performed, there is a risk of significant shrinkage and deformation of the molded body.

[0070] By using foamed particles having a Ca / A ratio of 0.01 or more and a Ct / A ratio of 0.02 or more, the water cooling time of the molded body in the molding die can be shortened, and a molded body having a complex shape with excellent surface properties and weldability can be formed. From the viewpoint of further improving the effect, the Ca / A ratio is preferably 0.02 or more. From the same viewpoint, the Ct / A ratio is preferably 0.03 or more.

[0071] On the other hand, when the ratio Ca / A of the average cross-sectional area Ca of each defect portion to the average cross-sectional area A of the foamed particles and / or the ratio Ct / A of the total cross-sectional area Ct of the defect portions to the average cross-sectional area A of the foamed particles is too large, there is a risk of reducing the secondary foaming property of the foamed particles. In addition, there is a risk of causing the surface property (appearance) of the obtained molded body to deteriorate and the rigidity to decrease. By using foamed particles having a ratio Ca / A of less than 0.20 and a ratio Ct / A of less than 0.20, a molded body with excellent surface property and rigidity can be easily obtained.

[0072] From the viewpoint of more reliably avoiding the deterioration of the surface property and the reduction of the rigidity of the molded body, the ratio Ca / A is preferably 0.15 or less, more preferably 0.10 or less, and further preferably 0.08 or less. From the same viewpoint, the ratio Ct / A is preferably 0.18 or less, more preferably 0.15 or less, further preferably 0.10 or less, and particularly preferably 0.08 or less. In addition, the calculation method of the average cross-sectional area A of the foamed beads, the average cross-sectional area Ca of each defect, and the total cross-sectional area Ct of the defect will be described later.

[0073] When forming the preferred range of the value of the ratio Ca / A, the upper limit and lower limit of the above-mentioned ratio Ca / A can be arbitrarily combined. For example, the preferred range of the value of the ratio Ca / A can be above 0.02 and below 0.15, or above 0.02 and below 0.10, or above 0.02 and below 0.08. Similarly, when forming the preferred range of the value of the ratio Ct / A, the upper limit and lower limit of the above-mentioned Ct / A can be arbitrarily combined. For example, the preferred range of the value of the ratio Ct / A can be above 0.03 and below 0.18, or above 0.03 and below 0.15, or above 0.03 and below 0.10, or above 0.03 and below 0.08.

[0074] In addition, in the crack filling process, the average length L in the opening and closing direction is A In the specific range, a molding die having a molding cavity having a first portion and a second portion is used, and the size of the slit gap δ is set to the minimum value P1 of the compression rate of the first portion. min The maximum compression ratio of the second part P2 max Difference P2 max -P1 min The difference in compression rate P2 in the crack filling step is 5% or more and 100% or less, thereby making it easy to obtain a molded body having a thick portion and a thin portion and having excellent surface properties and weldability. max -P1 min If the thickness is too large, there is a risk of poor welding of the foamed particles in the thick portion of the obtained molded body and the portion with high compression rate when filling the crack. In addition, there is a risk of reducing the toughness of the obtained molded body. In addition, there is a risk of difficulty in suppressing the shrinkage and deformation of the molded body when the curing step is omitted.

[0075] In the manufacturing method, as needed, an internal pressure imparting process can be performed to impart internal pressure to the foamed particles before being filled into the forming mold. When the internal pressure imparting process is performed, the internal pressure of the foamed particles filled in the forming mold can be appropriately set, for example, from a range below 0.3 MPa (G) (G: gauge pressure). The internal pressure of the foamed particles is preferably below 0.20 MPa (G). In addition, molding can also be performed without imparting internal pressure to the foamed particles. In addition, the pressure (internal pressure) inside the bubbles can be measured, for example, by the method described in Japanese Patent Gazette No. 2003-201361.

[0076] In the manufacturing method, the specific method of forming the cavity is as long as the minimum value P1 of the compression rate in the first part is min The maximum compression ratio P2 in the second part max Difference P2 max -P1min and the average length L A The method that satisfies the above-mentioned specific range is not particularly limited, and can be set to a method corresponding to the shape of the desired molded body. For example, from the viewpoint of making the above-mentioned effect more beneficial, the average length L in the opening and closing direction of the molding cavity is A The average length L of the molding cavity in the opening and closing direction is preferably 15 mm or more, and more preferably 20 mm or more. A The upper limit is approximately 500 mm, preferably 300 mm, more preferably 200 mm, and further preferably 150 mm.

[0077] The average length L in the opening and closing direction of the molding cavity A When the preferred range is A For example, the average length L A The preferred range of may be 10 mm to 500 mm, 15 mm to 300 mm, 20 mm to 200 mm, or 20 mm to 150 mm.

[0078] The first portion of the molding cavity has a shape corresponding to the thick wall portion of the molding when the opening and closing direction of the molding die is set to the thickness of the molding. Figure 1 to Figure 3 The structure shown in FIG. 1 is such that the first portion 121 of the molding cavity 12 that can mold a bottomed box-shaped molding corresponds to the side wall of the molding. Figure 4 As shown, the maximum length L1 of the first portion of the molding cavity 12 configured to be able to mold a bottomed box-shaped molded body in the opening and closing direction is max The length of the portion corresponding to the side wall of the molded body in the opening and closing direction. The molding cavity may have one first portion or two or more first portions. When the molding cavity has two or more first portions, the shapes of the first portions may be the same or different from each other.

[0079] When the molding cavity has two or more first portions, the maximum length L1 of the first portion in the opening and closing direction is max The length in the opening and closing direction of the position where the length in the opening and closing direction is the longest among the plurality of first parts, and the minimum value P1 of the compression rate min is based on the length L1 at this position max The calculated compression ratio.

[0080] The second portion of the molding cavity has a shape corresponding to the thin-walled portion of the molding when the opening and closing direction of the molding die is set to the thickness of the molding. Figure 1 to Figure 3The second portion 122 of the molding cavity 12 that is configured to mold a bottomed box-shaped molded body corresponds to the bottom wall of the molded body. Figure 4 As shown, the minimum length L2 in the opening and closing direction of the second portion 122 of the molding cavity 12 configured to be able to mold a bottomed box-shaped molded body is min The length of the portion corresponding to the bottom wall of the molded body in the opening and closing direction. The molding cavity may have one second portion or two or more second portions. When the molding cavity has two or more second portions, the shapes of the second portions may be the same or different from each other.

[0081] When the molding cavity has two or more second portions, the minimum length L2 of the second portion in the opening and closing direction is min The maximum value P2 of the compression ratio is the length in the opening and closing direction of the position where the length in the opening and closing direction is the shortest among the plurality of second parts. max is based on the length L2 at this position min The calculated compression ratio.

[0082] The maximum value L1 of the length of the first portion in the opening and closing direction of the forming die max It is preferably 30 mm or more, more preferably 45 mm or more, and further preferably 55 mm or more. As described above, according to the manufacturing method, even when it is desired to form a molded body having a shape with portions having different thicknesses, the heating medium can be efficiently supplied throughout the entire molding cavity, and the welding property between the foamed particles can be improved. In addition, even when the maximum length L1 of the first portion is max For example, when the diameter is relatively large, such as 55 mm or more, it is also possible to more easily avoid a decrease in the weldability of the foamed beads filled in the first part. For example, according to the manufacturing method, the weldability of the portion corresponding to the first part in the obtained thermoplastic resin foamed bead molded body can be preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more.

[0083] The size of the gap in the gap filling process δ (unit: mm) is as follows Figure 4 1 and 2 show the movement amount of the movable mold 13 in the opening and closing direction from the position M1 in the state where the filling of the molding cavity 12 with the foamed beads 2 is completed to the position M2 in the state where the molding die 1 is completely closed.

[0084] Preferably, in the crack filling step, the maximum value P2 of the compression rate of the second portion is max The size δ of the slit gap is set to be greater than 25% and less than 150%. According to the manufacturing method, even if the maximum value P2 of the compression rate of the second portionmax When the value is relatively large as described above, it is also possible to easily avoid a decrease in the weldability of the foamed beads filled in the second part. From the viewpoint of more reliably obtaining this effect, the maximum value P2 of the compression rate in the second part is max On the other hand, from the viewpoint of being able to more easily avoid a decrease in the weldability between the foamed particles, the maximum value P2 of the compression ratio in the second part is max More preferably, it is 120% or less.

[0085] The maximum value P2 of the compression ratio in the second part max When the preferred range is set, the maximum compression ratio P2 mentioned above can be arbitrarily combined. max For example, the maximum compression ratio P2 max The preferred range of may be 30% or more and 120% or less.

[0086] In the in-mold forming process, the foamed particles are heated by supplying a heating medium such as steam into the forming cavity. The forming temperature during in-mold forming can be controlled by the forming pressure, that is, the pressure of the heating medium supplied to the forming cavity. If the forming temperature (i.e., the forming pressure) during in-mold forming is increased, the foamed particles are easily welded to each other, but on the other hand, there is a tendency for the water cooling time in the forming mold to become longer. On the other hand, if the forming temperature is reduced, the water cooling time in the forming mold can be shortened, but on the other hand, there is a tendency for the foamed particles to be difficult to weld to each other. From the viewpoint of the production efficiency of the formed body, it is preferably formed with a forming pressure as low as possible. From this viewpoint, the forming pressure is preferably set to a range of 0.18MPa (G) or more and 0.30MPa (G) or less, and more preferably set to a range of 0.22MPa (G) or more and 0.28MPa (G) or less, for example, in terms of a gauge pressure.

[0087] In the manufacturing method, a curing step of allowing the molded body to stand for a predetermined time in a high temperature atmosphere adjusted to, for example, about 60° C. to 80° C. may be performed as needed. However, even if the molded body is not subjected to the curing step in a high temperature atmosphere, shrinkage and deformation of the molded body can be suppressed. When the curing step is omitted, for example, the molded body can be stabilized in shape by allowing the molded body to stand for 12 hours or more in an environment of, for example, 23° C.

[0088] (Foamed particle molded body)

[0089] The molded body obtained by the manufacturing method has an open cell structure. The open cell structure is a tiny space portion connected to the outside of the molded body. The open cell structure is formed by the interconnection of multiple defective parts of the foamed particles such as through holes and grooves, the connection of defective parts of the foamed particles with the voids formed between the foamed particles, the connection of voids between the foamed particles, and the continuous cell parts of the foamed particles constituting the molded body.

[0090] The compact density is preferably 10 kg / m 3 Above and 150kg / m 3 In this case, the lightness and rigidity of the molded body can be improved in a balanced manner. From the viewpoint of further improving the rigidity of the molded body, the density of the molded body is more preferably 15 kg / m 3 More preferably, 20 kg / m 3 From the viewpoint of further improving the lightness of the molded body, the density of the molded body is more preferably 60 kg / m 3 Below, more preferably 50kg / m 3 Below, particularly preferably 45kg / m 3 The density of the molded body is calculated by dividing the mass of the molded body (unit: g) by the volume (unit: L) obtained from the outer dimensions of the molded body and converting the units. In addition, for example, when the molded body has a complex shape at least in part and the volume is not easy to obtain from the outer dimensions of the molded body, the volume of the molded body can be obtained by water.

[0091] When forming the preferred range of the molded body density, the upper limit and lower limit of the molded body density mentioned above can be arbitrarily combined. For example, the preferred range of the molded body density can be 10 kg / m 3 Above and 60kg / m 3 Below, can also be 15kg / m 3 Above and 50kg / m 3 Below, can also be 20kg / m 3 Above and 45kg / m 3 the following.

[0092] In the past, when manufacturing a molded body with a low density, the molded body tends to deform significantly after demolding, so it is particularly difficult to omit the curing step. In contrast, the foamed bead molded body can omit the curing step even when the density is low, and even without curing, it has a desired shape and excellent appearance and rigidity. From the viewpoint of more effectively exerting this effect, it is also preferred that the density of the molded body is set to the above range.

[0093] From the viewpoint of being able to more reliably obtain the effect of suppressing significant shrinkage and deformation of the molded body without performing the curing step, the porosity of the molded body is preferably 4% or more, more preferably 5% or more. In addition, from the viewpoint of further improving the rigidity and appearance of the molded body, the porosity of the molded body is preferably 12% or less, more preferably 10% or less, and further preferably 8% or less. The porosity of the molded body is preferably within the above range in both the portion corresponding to the first portion and the portion corresponding to the second portion in the molded body.

[0094] When forming the preferred range of the porosity of the molded body, the above upper and lower limits of the porosity may be arbitrarily combined. For example, the preferred range of the porosity of the molded body may be 5% to 10%, or 5% to 8%.

[0095] The porosity of the formed body is measured and calculated, for example, as follows. Specifically, first, a test piece of a rectangular shape (for example, 20 mm long × 100 mm wide × 20 mm high) is cut out from the center of the formed body. Next, the test piece is sunk into a measuring cylinder filled with ethanol, and the true volume Vc (unit: L) of the test piece is calculated from the amount of rise in the liquid level of ethanol. In addition, the apparent volume Vd (unit: L) is calculated from the outer dimensions of the test piece. The porosity (unit: %) of the formed body is expressed by the following formula (4) using the true volume Vc and apparent volume Vd of the test piece obtained as described above.

[0096] Void ratio = [(Vd-Vc) / Vd] × 100 (4)

[0097] The 50% compressive stress of the molded body is preferably 200 kPa or more, and more preferably 220 kPa or more. In this case, the rigidity of the molded body can be further improved. The 50% compressive stress of the molded body can be determined based on JIS K6767:1999.

[0098] The molded article can also be used as a sound absorbing material, a shock absorbing material, a cushioning material, and the like in various fields such as the vehicle field such as automobiles and the construction field.

[0099] (Thermoplastic resin foam particles)

[0100] The foamed particles used in the manufacturing method have a columnar shape and have one or more defective parts selected from the group consisting of a through hole that axially penetrates the inside of the foamed particles and a groove that extends axially on the side circumference of the foamed particles. If the foamed particles have defective parts, it is easier to form an open cell structure in the molded body.

[0101] <Foamed particles having through holes>

[0102] Figure 5 as well as Figure 6 An example of the foamed beads 2 having the through-holes 211 as the defective portions 21 is shown. Figure 5 The foamed beads 2 shown have a cylindrical shape with through holes 211. The overall shape of the foamed beads can be, for example, a cylindrical shape or a prism shape. The through holes preferably penetrate the axial direction of the foamed beads. The number of through holes can be one or more.

[0103] In the case where the foamed particles have the through holes as defective portions, the average pore size d of the through holes is preferably greater than 0.1 mm and less than 1 mm. In this case, the Ca / A and / or Ct / A of the foamed particles can be easily adjusted to the above range. By setting the average pore size d of the through holes to greater than 0.1 mm, it is possible to prevent the through holes of the foamed particles from being flattened and clogged during in-mold molding, and the effect of the through holes can be more reliably exerted. From the same point of view, the average pore size d of the through holes is more preferably greater than 0.2 mm, and further preferably greater than 0.4 mm.

[0104] In the case where the average pore size d of the through-holes is too large, there is a risk that the Ca / A and / or Ct / A of the foamed particles will become too large. Therefore, there is a risk that gaps between the foamed particles, bumps on the through-holes, etc. are easily formed on the surface of the molded body. In addition, in this case, there is a risk that the rigidity of the molded body is reduced. On the other hand, if the size δ of the crack gap of the foamed particles is further increased in order to avoid the formation of such gaps between the foamed particles, bumps on the through-holes, etc., there is a risk that the density of the molded body becomes significantly higher, making it difficult to obtain a lightweight molded body. In addition, if the size δ of the crack gap is further increased, it is necessary to excessively increase the difference in compression rate P2. max -P1 min , there is a hidden danger that the molding temperature required to obtain a good molded body becomes significantly higher. In addition, in this case, when the curing step is omitted, there is a hidden danger that the significant shrinkage and deformation of the molded body cannot be suppressed. These problems can be easily avoided by setting the average pore size d of the through holes to be less than 1 mm. From the same point of view, the average pore size d of the through holes is more preferably less than 0.95 mm, further preferably less than 0.9 mm, and particularly preferably less than 0.85 mm.

[0105] When constituting the preferred range of the average pore size d of the through hole, the upper limit and lower limit of the above-mentioned average pore size d can be arbitrarily combined. For example, the preferred range of the average pore size d can be 0.2 mm or more and 0.95 mm or less, 0.2 mm or more and 0.9 mm or less, or 0.4 mm or more and 0.85 mm or less.

[0106] The average pore size d of the through-holes 211 of the foamed beads 2 is obtained as follows. First, the foamed beads 2 are cut at the center of the axial direction with a plane perpendicular to the axial direction, as shown in FIG. Figure 6 The cut surface is exposed as shown. Next, a photograph of the cut surface is taken, and the cross-sectional area (specifically, the opening area) of the through hole in the cut surface is calculated. Then, the diameter of an imaginary perfect circle having the same area as the cross-sectional area of ​​the through hole is calculated, and this value is used as the pore size of the through hole of each foamed particle. The above operation is performed on more than 50 foamed particles, and the arithmetic mean of the pore size of the through hole obtained is used as the average pore size d of the through hole of the foamed particles. In addition, even if the size of the through hole of each foamed particle is such that the through hole diameter is different in the through direction, the through hole diameter of each foamed particle is determined by the pore diameter of the through hole in the cut surface as described above.

[0107] The average pore size d of the through holes can be adjusted to the specific range by adjusting the size of the average pore size dr of the through holes in the resin particles described later, the apparent density of the foamed particles, etc. In addition, by making the foamed particles into secondary foamed particles produced by secondary foaming, the average pore size d can be more easily adjusted to a small value.

[0108] From the viewpoint of increasing the wall thickness of the foamed beads to improve the secondary foaming property of the foamed beads and the rigidity of the molded body, and from the viewpoint of being able to more reliably suppress the deformation and shrinkage of the molded body when the curing process is omitted, the average outer diameter D of the foamed beads is preferably 2 mm or more, more preferably 2.5 mm or more, and further preferably 3 mm or more. On the other hand, from the viewpoint of improving the filling property of the foamed beads into the molding die, the average outer diameter D of the foamed beads is preferably 8 mm or less, more preferably 5 mm or less, and further preferably 4.5 mm or less.

[0109] When constituting the preferred range of the average outer diameter D of the foamed beads, the upper limit and lower limit of the above-mentioned average outer diameter D can be arbitrarily combined. For example, the preferred range of the average outer diameter D can be 2 mm or more and 8 mm or less, 2.5 mm or more and 5 mm or less, or 3 mm or more and 4.5 mm or less.

[0110] The ratio d / D of the average pore size d of the through-holes to the average outer diameter D of the foamed particles is preferably 0.4 or less, more preferably 0.35 or less, further preferably 0.3 or less, and particularly preferably 0.25 or less. By making the ratio d / D 0.4 or less, the secondary foaming property of the foamed particles during in-mold forming can be appropriately improved, and a molded body with excellent surface properties and rigidity can be more easily obtained. On the other hand, with regard to d / D, from the viewpoint of further suppressing the through-holes of the foamed particles from being flattened and blocked during in-mold forming and more reliably exerting the effect of the through-holes, the ratio d / D is preferably 0.1 or more. In addition, the calculation method of the average outer diameter D of the foamed particles will be described later.

[0111] When forming the preferred range of the value of the ratio d / D, the upper limit and lower limit of the above ratio d / D can be arbitrarily combined. For example, the preferred range of the value of the ratio d / D can be 0.1 or more and 0.4 or less, 0.1 or more and 0.35 or less, 0.1 or more and 0.3 or less, or 0.1 or more and 0.25 or less.

[0112] The average wall thickness t of the foamed particles with through holes is preferably 1.0 mm or more and 2.0 mm or less. If the average wall thickness t is within this range, the wall thickness of the foamed particles is thick enough, so the secondary foaming property during in-mold forming is further improved. In addition, the foamed particles are less likely to be flattened relative to external forces, and the rigidity of the molded body is further improved. From this viewpoint, the average wall thickness t of the foamed particles is more preferably 1.2 mm or more.

[0113] The average wall thickness t of the foamed beads is the distance from the surface of the foamed beads (ie, the outer surface) to the outer edge of the through-hole (ie, the inner surface of the foamed beads), and is a value obtained by the following formula (5).

[0114] t=(Dd) / 2 ··· (5)

[0115] d: average diameter of through holes (unit: mm)

[0116] D: Average outer diameter of foamed particles (unit: mm)

[0117] In addition, the ratio t / D of the average wall thickness t of the foamed particles relative to the average outer diameter D is preferably greater than 0.30 and less than 0.50. If t / D is within the above range, the filling property of the foamed particles becomes better during the in-mold forming of the foamed particles. In addition, the water cooling time can be maintained shorter, and the secondary foaming property can be further improved. Thus, a molded body with excellent appearance and rigidity can be manufactured with good productivity at a lower forming heating temperature. From this viewpoint, the ratio t / D of the average wall thickness t of the foamed particles relative to the average outer diameter D is more preferably greater than 0.32, and more preferably greater than 0.35.

[0118] <Foamed particles having grooves>

[0119] Figure 7 as well as Figure 8 An example of the foamed beads 2 having the grooves 212 as the defective portions 21 is shown. Figure 7 The foamed particles 2 shown have a columnar shape and have at least one groove 212 on the side circumference thereof.

[0120] The above-mentioned "groove" refers to a concave portion provided on the side circumference of the foamed bead 2 and extending along the axial direction of the foamed bead 2. More specifically, Figure 8 As shown, the groove 212 of the foamed bead 2 is observed as a portion where the outline of the foamed bead 2 is recessed inward in a cross section obtained when the foamed bead 2 is cut along a plane perpendicular to the axial direction of the foamed bead 2 .

[0121] The shape of the foamed particles 2 can be various. Figure 7 as well as Figure 8 As shown, the foamed bead 2 may be a columnar shape having a cross-shaped cross section perpendicular to the axial direction. The foamed bead 2 having such a shape has four grooves 212 on its side surface. The cross-sectional shape of the foamed bead in the cross section perpendicular to the axial direction is not limited to Figure 7 as well as Figure 8 The shape can be, for example, a shape based on a circle, a shape based on a triangle, a shape based on a quadrilateral, or the like.

[0122] The number of grooves 212 provided in the foamed beads may be one or more. Figure 7 as well as Figure 8 The V-shape shown may be in various forms such as a semicircular shape, a quadrilateral shape, and a U-shape. When the foamed beads have two or more grooves 212, all the grooves 212 may have the same cross-sectional shape or different cross-sectional shapes.

[0123] The foamed beads preferably have 2 or more and 6 or less grooves. In this case, it is easier to form an open cell structure in the molded body. Therefore, even if the curing step is omitted, the molded body is less likely to deform.

[0124] In addition, when the foamed beads have two or more grooves, the grooves are preferably arranged at equal intervals on the side circumference of the foamed beads. In other words, when the foamed beads have multiple grooves, the grooves are preferably arranged at positions symmetrical with respect to the central axis of the foamed beads. If such foamed beads are molded in-mold, it is easier to form an open bubble structure in the molded body. Therefore, even if the curing step is omitted, the molded body is less likely to deform.

[0125] <Average cross-sectional area Ca and total cross-sectional area Ct per defect>

[0126] In the cross section obtained by cutting the foamed beads at the center of the axial direction with a plane perpendicular to the axial direction, the ratio Ca / A of the average cross-sectional area Ca of each defect to the average cross-sectional area A of the foamed beads is 0.01 or more and 0.20 or less, and the ratio Ct / A of the total cross-sectional area Ct of the defects to the average cross-sectional area A of the foamed beads is 0.02 or more and 0.20 or less. As described above, in the manufacturing method, by using the foamed beads having the specific shape, the water cooling time of the molded body in the mold can be shortened, and even in the case of a complex shape, a molded body with excellent surface properties and weldability can be easily obtained.

[0127] The method for calculating the average cross-sectional area A of the foamed beads is as follows. First, the foamed beads are cut at the center of the axial direction with a plane perpendicular to the axial direction to expose the cut surface. The cross-sectional area of ​​the foamed beads 2 in the cut surface is measured. For example, Figure 6 as well as Figure 8 When the foamed beads 2 are composed of only the foamed layer 3 as shown in FIG. 1 , the cross-sectional area of ​​the foamed beads 2 is equal to the cross-sectional area of ​​the foamed layer 3 in the cut surface. Fig.10 When the foamed particle 2 has a foamed layer 3 and a weldability improving layer 4 covering the foamed layer 3 as shown, the cross-sectional area of ​​the foamed particle 2 is the sum of the cross-sectional area of ​​the foamed layer 3 in the cut surface and the cross-sectional area of ​​the weldability improving layer 4. In addition, the cross-sectional area of ​​the foamed particle 2 in the cut surface can be measured, for example, by taking a photograph of the cut surface of the foamed particle and performing image analysis. In addition, the cross-sectional area of ​​the defective portion is not included in the cross-sectional area of ​​the foamed particle.

[0128] The above operation is performed for 100 or more expanded beads, and the arithmetic mean value of the cross-sectional areas of the obtained expanded beads is defined as the average cross-sectional area A of the expanded beads in the cut surface.

[0129] The average cross-sectional area Ca of each defect and the total cross-sectional area Ct of the defects are calculated as follows. First, the foamed beads are cut at the center of the axial direction with a plane perpendicular to the axial direction to expose the cut surface. Figure 6 as well as Fig.10 When the defective portion 21 is a through hole 211 as shown, the cross-sectional area C of the through hole 211 in the cut surface is measured.

[0130] In addition, when the defect 21 is a groove 212, as shown in FIG. Figure 8As shown in FIG. 1 , a tangent line L1 is drawn on the outside of each groove 212 in the cut surface, which is tangent to the outline of the foamed bead 2 at two points Q1 and Q2 and does not pass through the inside of the foamed bead 2. Then, the area of ​​the region surrounded by the outline of the foamed bead 2 and the tangent line L1 is calculated, and the area is taken as the cross-sectional area C of each groove 212. That is, the cross-sectional area C of each groove 212 is Figure 8 The area of ​​the region indicated by the diagonal line.

[0131] The total cross-sectional area C of the through-hole 211 and the cross-sectional area of ​​the groove 212 thus obtained are summed up to calculate the total cross-sectional area of ​​the defective portion 21 in each foamed bead 2. In addition, the total cross-sectional area of ​​the defective portion 21 is divided by the number of defective portions 21 to calculate the cross-sectional area of ​​each defective portion in each foamed bead 2.

[0132] The above operation is performed for 100 or more expanded beads, and the arithmetic mean of the total cross-sectional areas of the obtained defects is taken as the total cross-sectional area Ct of the defects. Also, the average cross-sectional area of ​​each defect is taken as the average cross-sectional area Ca of each defect.

[0133] The method for calculating the average outer diameter D of the foamed beads is as follows. First, the foamed beads 2 are cut at the center of the axial direction with a plane perpendicular to the axial direction, so that Figure 6 as well as Figure 8 The cut surface as shown in the figure is exposed. Two points Q3 and Q4 with the longest distance between each other are determined on the outline of the foamed particle 2 in the cut surface, and the distance between these two points (that is, the maximum outer diameter of the foamed particle in the cut surface) is taken as the outer diameter r of each foamed particle 2. Then, the arithmetic mean of the outer diameters r measured for more than 100 foamed particles 2 is taken as the average outer diameter D of the foamed particles. In addition, the measurement of the outer diameter of the foamed particles 2 in the cut surface can be performed, for example, by taking a photograph of the cut surface of the foamed particles and performing image analysis. In addition, even if the outer diameters of the foamed particles are different in the through-direction, the outer diameter of each foamed particle is determined by the outer diameter at the cut surface as described above.

[0134] <Apparent density and bulk density of foamed particles>

[0135] The bulk density of the foamed particles is preferably 10 kg / m 3 Above and 50kg / m 3 Below, more preferably 20kg / m 3 Above and 35kg / m 3In this case, the lightness and rigidity of the molded body can be improved in a balanced manner. In addition, in the past, especially when manufacturing a molded body with a low density (i.e., a molded body with a high molded body ratio), the molded body is easily deformed after demolding, and it is difficult to omit the curing process. In contrast, the foamed particles can omit the curing process even when the apparent density is low, so a molded body with a good appearance can be manufactured even without curing.

[0136] The ratio of the apparent density of the foamed particles to the bulk density of the foamed particles (i.e., apparent density / bulk density) is preferably greater than 1.6, and more preferably greater than 1.7. In this case, the water cooling time after in-mold forming can be further shortened, and a lightweight and good foamed particle molded body can be obtained more easily. In addition, the deformation and shrinkage of the molded body when the curing process is omitted can be more reliably suppressed. In addition, the ratio of the apparent density of the foamed particles to the bulk density of the foamed particles (i.e., apparent density / bulk density) is preferably less than 2.0, and more preferably less than 1.9. In this case, the surface properties and rigidity of the obtained molded body can be made better.

[0137] When constituting the preferred range of the value of the ratio of the apparent density of the foamed beads to the bulk density of the foamed beads, the upper limit and lower limit of the above ratio can be arbitrarily combined. For example, the preferred range of the value of the apparent density / bulk density can be 1.7 or more and less than 2.0, or 1.7 or more and 1.9 or less.

[0138] The calculation method of the bulk density of the foamed particles is as follows. First, the foamed particles are allowed to stand for more than 24 hours in an environment with a relative humidity of 50%, a temperature of 23°C, and an air pressure of 1 atm to adjust the state of the foamed particles. The foamed particle group after the state adjustment is filled into a measuring cylinder in a naturally stacked manner, and the bulk volume of the foamed particle group (unit: L) is read from the scale of the measuring cylinder. Then, by converting the value obtained by dividing the mass of the foamed particle group in the measuring cylinder (unit: g) by the above-mentioned bulk volume, the bulk density of the foamed particles (unit: kg / m 3 ). The bulk density of the expanded particles is a value measured using the expanded particles in a natural state without being compressed under an environment with an air pressure of 1 atm.

[0139] The method for calculating the apparent density of the foamed particles is as follows. First, the foamed particle group is allowed to stand for 1 day in an environment of relative humidity of 50%, temperature of 23°C, and air pressure of 1 atm to adjust the state of the foamed particles. After measuring the mass (unit: g) of the foamed particle group, use a metal mesh to sink it into a measuring cylinder filled with alcohol (such as ethanol) at 23°C, and calculate the volume (unit: L) of the foamed particle group from the amount of liquid level rise. Thereafter, the apparent density (unit: kg / m 3 ).

[0140] <Foaming layer>

[0141] The foamed particles have a foaming layer with a thermoplastic resin as a base resin. The thermoplastic resin constituting the foaming layer is preferably a crystalline thermoplastic resin with crystallinity such as a polyolefin resin, a polyamide resin, and a crystalline polyester resin, etc., such as a polypropylene resin and a polyethylene resin. In addition, in this specification, a polypropylene resin refers to a homopolymer of a propylene monomer and a propylene copolymer containing more than 50% by mass of a structural unit from propylene. In addition, a polyethylene resin refers to a homopolymer of an ethylene monomer and an ethylene copolymer containing more than 50% by mass of a structural unit from ethylene.

[0142] In addition, in this specification, polyamide resin refers to polyamide and polyamide copolymer. When the base material resin of the foaming layer is a polyamide resin, the polyamide resin constituting the foaming layer is preferably a polyamide copolymer. As a polyamide copolymer, for example, polycaprolactam / polyhexamethylene adipamide copolymer (nylon 6 / 66), caprolactam / hexamethylenediaminodipic acid / lauryl lactam (nylon 6 / 66 / 12) and caprolactam / lauryl lactam copolymer (nylon 6 / 12) etc. can be cited.

[0143] In the present specification, "having crystallinity" means that the endothermic peak heat quantity associated with melting of the resin obtained by using a DSC curve at a heating rate of 10°C / min using a heat flux differential scanning calorimeter according to "when the heat of fusion is measured after a certain heat treatment" described in JIS K7122 (1987) (the heating rate and cooling rate in the state adjustment of the test piece are both set to 10°C / min) is 5 J / g or more. The endothermic peak heat quantity is preferably 15 J / g or more, and more preferably 30 J / g or more.

[0144] The foaming layer may contain other polymers other than the thermoplastic resin within the range that does not hinder the above-mentioned effect. As other polymers, elastomers etc. can be exemplified. The content of other polymers in the foaming layer is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 0, that is, the foaming layer substantially contains only thermoplastic resin as polymer.

[0145] In addition, the thermoplastic resin as the base resin of the foaming layer may contain additives such as a bubble regulator, a crystal nucleating agent, a flame retardant, a flame retardant aid, a plasticizer, an antistatic agent, an antioxidant, an ultraviolet light blocking agent, a light stabilizer, a conductive filler, an antibacterial agent, and a colorant within the range that does not impair the above-mentioned effects. The content of the additive in the foaming layer is preferably 0.01 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the thermoplastic resin.

[0146] The thermoplastic resin constituting the foaming layer is preferably a polyolefin resin. In addition, the thermoplastic resin constituting the foaming layer is preferably a polypropylene resin among polyolefin resins, and more preferably a propylene copolymer formed by copolymerization of propylene and other monomers. In this case, the content of other polymers other than the polypropylene resin in the foaming layer is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 0, that is, the foaming layer substantially contains only the polypropylene resin as a polymer.

[0147] As the propylene copolymer, preferably, ethylene-propylene copolymer, butene-propylene copolymer, hexene-propylene copolymer, ethylene-propylene-butene copolymer and the like copolymer of propylene and α-olefin having 4 to 10 carbon atoms can be exemplified. These copolymers can be, for example, random copolymers or block copolymers, preferably random copolymers. In addition, the foaming layer can contain one polypropylene resin or two or more polypropylene resins.

[0148] The thermoplastic resin constituting the foaming layer is particularly preferably an ethylene-propylene random copolymer comprising an ethylene component of more than 0.5 mass % and less than 3.5 mass % among these polypropylene resins. According to the foaming particles possessing such a foaming layer, it is possible to more easily obtain excellent in-mold formability, and excellent rigidity and surface properties, and a molded body that can suppress deformation and shrinkage even when curing steps are omitted. In addition, in this case, the secondary foaming of the foaming particles can be further improved, and a molded body with a large difference in thickness can be more easily manufactured.

[0149] From the viewpoint of further improving the moldability of the expanded beads and obtaining a molded article having excellent energy absorption properties, the content of the ethylene component in the ethylene-propylene random copolymer is preferably 2.0% by mass or more and 3.5% by mass or less.

[0150] In addition, the above-mentioned "ethylene component" and "propylene component" refer to the structural unit derived from ethylene and the structural unit derived from propylene in the ethylene-propylene copolymer, respectively. In addition, the content of the ethylene component is the mass ratio of the ethylene component when the total of the ethylene component and the propylene component is set to 100% by mass. The content of each component in the ethylene-propylene copolymer can be obtained based on the result of IR spectrum measurement.

[0151] When the base resin of the foaming layer is a polypropylene resin, the melting point Tmc of the polypropylene resin is preferably below 155°C. In this case, a molded body with excellent appearance and rigidity can be formed at a lower molding temperature (i.e., a low molding pressure). From the viewpoint of improving this effect, the melting point Tmc of the polypropylene resin constituting the foaming layer is preferably below 150°C, and more preferably below 145°C. On the other hand, from the viewpoint of further improving the heat resistance and mechanical strength of the molded body, the melting point Tmc of the polypropylene resin constituting the foaming layer is preferably above 135°C, more preferably above 138°C, and further preferably above 140°C.

[0152] When constituting the preferred range of the melting point Tmc value of the polypropylene resin constituting the foaming layer, the upper limit and lower limit of the melting point Tmc described above may be arbitrarily combined. For example, the preferred range of the melting point Tmc may be 135°C to 155°C, 138°C to 150°C, or 140°C to 145°C.

[0153] In the case where the thermoplastic resin constituting the foaming layer is crystalline, the melting point of the thermoplastic resin can be determined based on the obtained DSC curve by differential scanning calorimetry (i.e., DSC) according to JIS K7121-1987. First, the state of the test piece is adjusted according to "(2) After a certain heat treatment, the melting temperature is measured". The state-adjusted test piece is heated from 30°C to 200°C at a heating rate of 10°C / min, thereby obtaining a DSC curve, and the vertex temperature of the melting peak appearing in the DSC curve is taken as the melting point Tmc of the thermoplastic resin. In addition, in the case where multiple melting peaks appear in the DSC curve, the vertex temperature of the melting peak with the largest area is taken as the melting point Tmc.

[0154] When the base resin of the foaming layer is a polypropylene resin, the melt mass flow rate (i.e., MFR) of the polypropylene resin is preferably 5 g / 10 minutes or more, more preferably 6 g / 10 minutes or more, and further preferably 7 g / 10 minutes or more. In this case, the foamability and formability can be further improved. On the other hand, from the viewpoint of further improving the rigidity of the molded body, the MFR of the polypropylene resin is preferably 12 g / 10 minutes or less, and more preferably 10 g / 10 minutes or less. In addition, the MFR of the polypropylene resin is a value measured based on JIS K7210-1:2014 under the conditions of a test temperature of 230°C and a load of 2.16 kg.

[0155] When constituting the preferred range of MFR of the polypropylene resin constituting the foaming layer, the upper limit and lower limit of the above-mentioned MFR can be arbitrarily combined. For example, the preferred range of MFR can be 5 g / 10 minutes or more and 12 g / 10 minutes or less, 6 g / 10 minutes or more and 12 g / 10 minutes or less, or 7 g / 10 minutes or more and 10 g / 10 minutes or less.

[0156] When the base resin of the foaming layer is a polypropylene resin, the bending elastic modulus of the polypropylene resin is preferably 800 MPa or more and 1600 MPa or less. From the viewpoint of improving the rigidity of the molded body and more reliably suppressing the dimensional change when the curing process is omitted, the bending elastic modulus of the polypropylene resin constituting the foaming layer is preferably 800 MPa or more, more preferably 850 MPa or more, and further preferably 900 MPa or more. On the other hand, from the viewpoint of being able to mold a molded body with excellent appearance and rigidity at a lower molding temperature (i.e., low molding pressure) and obtaining a foamed particle molded body with excellent energy absorption characteristics, the bending elastic modulus of the polypropylene resin constituting the foaming layer is preferably less than 1200 MPa, more preferably 1100 MPa or less, and further preferably 1000 MPa or less. In addition, the bending elastic modulus of the polypropylene resin can be obtained based on JIS K7171:2008.

[0157] When constituting the preferred range of the bending elastic modulus of the polypropylene resin constituting the foaming layer, the upper limit and lower limit of the above-mentioned bending elastic modulus can be arbitrarily combined.For example, from the viewpoint of improving the rigidity of the formed body, more reliably suppressing the viewpoint of the dimensional change under the situation of omitting the curing process, the bending elastic modulus of the polypropylene resin constituting the foaming layer can be more than 850MPa and less than 1600MPa, or more than 900MPa and less than 1600MPa.In addition, from the viewpoint of being able to form the formed body of outward appearance, excellent rigidity under lower forming temperature (that is, low forming pressure), the viewpoint of the foamed particle formed body that obtains excellent energy absorption characteristics, the bending elastic modulus of the polypropylene resin constituting the foaming layer can be more than 800MPa and less than 1200MPa, or more than 800MPa and less than 1100MPa, or more than 800MPa and less than 1000MPa.

[0158] In the past, especially when foamed beads made of a polypropylene resin having a bending elastic modulus of less than 1200 MPa were molded in-mold, the molded body after demolding tended to shrink and deform significantly if the curing step was omitted, probably because the resistance to shrinkage and deformation after demolding was small. In contrast, according to the above-mentioned method for manufacturing a molded body, for example, even when foamed beads made of a polypropylene resin having a bending elastic modulus of less than 1200 MPa are used, shrinkage and deformation of the molded body can be easily suppressed, and the curing step can be omitted.

[0159] When the base resin of the foaming layer is a polyamide resin, the bending modulus of the polyamide resin is preferably 800 MPa or more and 1600 MPa or less, and more preferably 1000 MPa or more and 1600 MPa or less. If the bending modulus of the polyamide resin is within the above range, it is different from the amide elastomer having a bending modulus of about 600 MPa or less. Even if it is exposed to room temperature after foaming, it is not easy to shrink, and it is easy to obtain foamed particles with a small apparent density. In addition, it is possible to more reliably suppress the dimensional change when the curing process is omitted. In addition, the bending modulus of the polyamide resin can be obtained based on JIS K7171: 2008. In addition, the melting point of the polyamide resin is preferably 180°C or more and 250°C or less.

[0160] In addition, when the base resin of the foaming layer is a polyamide resin, the melt mass flow rate (i.e., MFR) of the polyamide resin measured under the conditions of a test temperature of 230° C. and a load of 2.16 kg according to JIS K7210-1:2014 is preferably 1 g / 10 min or more and 8 g / 10 min or less, and more preferably 2 g / 10 min or more and 5 g / 10 min or less. In this case, the foamability and moldability can be further improved.

[0161] <Weldability Improvement Layer>

[0162] Alternatively, the foamed particles may include a foaming layer and a fusion-improving layer covering the foaming layer, and may have a multilayer structure in which the base resin of the foaming layer is a first thermoplastic resin and the base resin of the fusion-improving layer is a second thermoplastic resin. In this case, the fusion-improving layer may cover the entire surface of the foaming layer or may cover a portion of the foaming layer. For example, Fig. 9 as well as Fig.10 As shown, the weldability improving layer 4 may be provided on the side peripheral surface of the foamed beads 2 and cover the foamed layer 3 .

[0163] The weldability improving layer is a layer provided on the surface of the foamed particles in order to improve the weldability of the foamed particles in the in-mold forming. The second thermoplastic resin constituting the weldability improving layer preferably has a melting point or a low softening point lower than the melting point of the first thermoplastic resin as the base resin of the foaming layer. In addition, when the second thermoplastic resin constituting the weldability improving layer is a crystalline thermoplastic resin of the same type as the first thermoplastic resin constituting the foaming layer, the second thermoplastic resin preferably has a crystallinity lower than that of the first thermoplastic resin. By coating the foaming layer with such a thermoplastic resin, the foamed particles can be welded at a lower forming temperature (i.e., a low forming pressure) in the in-mold forming. As a result, the deformation and shrinkage of the molded body in the case where the curing process is omitted can be more reliably suppressed.

[0164] The second thermoplastic resin constituting the weldability improving layer may be a crystalline thermoplastic resin or a non-crystalline thermoplastic resin. As the crystalline thermoplastic resin used in the weldability improving layer, for example, polyolefin resins can be exemplified. In addition, as the non-crystalline thermoplastic resin used in the weldability improving layer, for example, polystyrene resins can be exemplified. In the case where the foaming layer is composed of a polypropylene resin, from the viewpoint of adhesion to the foaming layer, the second thermoplastic resin constituting the weldability improving layer is preferably a polyolefin resin, more preferably a polyethylene resin and / or a polypropylene resin, and further preferably a polypropylene resin. As the polypropylene resin used as the second thermoplastic resin, for example, ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-propylene-butene copolymers, and propylene homopolymers can be cited. Among them, as the base resin of the weldability improving layer, ethylene-propylene copolymers and / or ethylene-propylene-butene copolymers are particularly preferably used.

[0165] When the second thermoplastic resin constituting the weldability improving layer is a crystalline thermoplastic resin, the difference Tmc-Tms between the melting point Tmc of the first thermoplastic resin constituting the foaming layer and the melting point Tms of the second thermoplastic resin constituting the weldability improving layer is preferably 5°C or more, more preferably 6°C or more, and even more preferably 8°C or more. In this case, the weldability of the foamed particles can be further improved, and the molding temperature can be further reduced. On the other hand, from the viewpoint of suppressing the peeling of the foaming layer and the weldability improving layer, the mutual adhesion between the foamed particles, etc., the difference Tmc-Tms between the melting point Tmc and the melting point Tms is preferably 35°C or less, more preferably 20°C or less, and even more preferably 15°C or less. The melting point of the second thermoplastic resin used in the weldability improving layer is determined based on JIS K7121:1987. More specifically, the melting point of the second thermoplastic resin used in the weldability improving layer can be determined by the same conditions and method as the first thermoplastic resin constituting the above-mentioned foaming layer.

[0166] When constituting the preferred range of the melting point difference Tmc-Tms value, the upper limit and lower limit of the melting point difference Tmc-Tms described above may be arbitrarily combined. For example, the preferred range of the melting point difference Tmc-Tms may be 5°C to 35°C, 6°C to 20°C, or 8°C to 15°C.

[0167] In addition, when the second thermoplastic resin constituting the weldability improving layer is a non-crystalline thermoplastic resin, the difference Tmc-Tss between the melting point Tmc of the first thermoplastic resin constituting the foaming layer and the softening point Tss of the second thermoplastic resin constituting the weldability improving layer is preferably 5°C or more, more preferably 6°C or more, and even more preferably 8°C or more. In this case, the weldability of the foamed particles can be further improved and the molding temperature can be further reduced. On the other hand, from the viewpoint of suppressing the peeling of the foaming layer and the weldability improving layer, the mutual adhesion between the foamed particles, etc., the difference Tmc-Tss between the melting point Tmc and the softening point Tss is preferably 35°C or less, more preferably 20°C or less. The softening point of the non-crystalline thermoplastic resin used in the weldability improving layer is the Vicat softening point measured by the A50 method based on JIS K7206:1999.

[0168] When forming the preferred range of the difference Tmc-Tss value, the upper limit and lower limit of the difference Tmc-Tss described above can be arbitrarily combined. For example, the preferred range of the difference Tmc-Tss may be 5°C to 35°C, 6°C to 20°C, or 8°C to 20°C.

[0169] The second thermoplastic resin constituting the weldability improving layer may contain additives such as a crystal nucleating agent, a flame retardant, a flame retardant aid, a plasticizer, an antistatic agent, an antioxidant, an ultraviolet light blocking agent, a light stabilizer, a conductive filler, an antibacterial agent, and a colorant, within a range not impairing the above-mentioned effects. The content of the additive in the weldability improving layer is preferably 0.01 parts by mass or more and 10 parts by mass or less, for example, relative to 100 parts by mass of the thermoplastic resin.

[0170] The weldability improving layer of the foamed particles may be in a foamed state or a non-foamed state, but is preferably in a substantially non-foamed state. "Substantially non-foamed" means a state in which the weldability improving layer is not foamed and does not contain bubbles, and a state in which bubbles disappear after foaming, and there is almost no bubble structure. The thickness of the weldability improving layer is, for example, 0.5 μm or more and 100 μm or less. In addition, an intermediate layer may be further provided between the foaming layer and the weldability improving layer.

[0171] From the viewpoint of maintaining the rigidity of the molded body and improving the moldability, the mass ratio (mass %) of the resin constituting the foaming layer to the resin constituting the weldability improving layer is preferably foaming layer: weldability improving layer = 99.5:0.5 to 80:20, more preferably 99:1 to 85:15, and further preferably 97:3 to 88:12.

[0172] When the thermoplastic resin constituting the foaming layer is a crystalline thermoplastic resin, the foamed particles preferably have a crystal structure as follows: in the DSC curve obtained when heated from 23°C to 200°C at a heating rate of 10°C / min, an endothermic peak caused by melting inherent to the crystalline thermoplastic resin constituting the foaming layer and one or more melting peaks located at a position closer to the high temperature side than the endothermic peak appear. Foamed particles having such a crystal structure have excellent mechanical strength and excellent formability. In addition, hereinafter, the endothermic peak caused by melting inherent to the crystalline thermoplastic resin appearing in the DSC curve is referred to as a "resin inherent peak", and the melting peak that appears at a position closer to the high temperature side than the resin inherent peak is referred to as a "high temperature peak". The resin inherent peak is generated by the endothermic absorption of the crystals originally possessed by the crystalline thermoplastic resin constituting the foaming layer when they melt. On the other hand, it is presumed that the high temperature peak is generated by the melting of secondary crystals formed in the crystalline thermoplastic resin constituting the foaming layer during the manufacturing process of the foamed particles. That is, it is presumed that when a high temperature peak appears in the DSC curve, secondary crystals are formed in the crystalline thermoplastic resin.

[0173] Whether the expanded beads have the above-mentioned crystal structure can be determined based on a DSC curve obtained by differential scanning calorimetry (DSC) under the above-mentioned conditions in accordance with JIS K7121: 1987. When performing DSC, 1 to 3 mg of the expanded beads can be used as a sample.

[0174] Specifically, in the DSC curve obtained when heating from 23°C to 200°C at a heating rate of 10°C / min as described above (i.e., the first heating), both the high temperature peak and the resin intrinsic peak of the crystalline thermoplastic resin constituting the foaming layer appear. In contrast, after the first heating, the DSC curve obtained when cooling from 200°C to 23°C at a cooling rate of 10°C / min and then heating from 23°C to 200°C at a heating rate of 10°C / min again (i.e., the second heating) only observes the resin intrinsic peak of the crystalline thermoplastic resin constituting the foaming layer. Thus, by comparing the DSC curve obtained during the first heating with the DSC curve obtained during the second heating, the resin intrinsic peak and the high temperature peak can be distinguished. The temperature of the top of the resin intrinsic peak is sometimes slightly different in the first heating and the second heating, but the difference is usually within 5°C.

[0175] From the viewpoint of further improving the moldability of the foamed particles and obtaining a molded body with better rigidity, the heat of fusion of the high temperature peak of the foamed particles is preferably from 5 J / g to 40 J / g, more preferably from 7 J / g to 30 J / g, and even more preferably from 10 J / g to 20 J / g.

[0176] The heat of fusion of the high temperature peak is determined as follows: First, 1 to 3 mg of the conditioned foamed beads are used as a sample and subjected to differential scanning calorimetry at a heating rate of 10°C / min from 23°C to 200°C to obtain a DSC curve. Fig.11 An example of a DSC curve is shown. In the case where the foamed particles have a high temperature peak, such as Fig.11 As shown, in the DSC curve, there appear a resin-specific peak ΔH1 and a high-temperature peak ΔH2 having a peak at a higher temperature side than the peak of the resin-specific peak ΔH1.

[0177] Next, a straight line L2 is drawn connecting point α corresponding to 80°C on the DSC curve and point β corresponding to the melting end temperature T of the foamed beads. The melting end temperature T is the end point on the high temperature side of the high temperature peak ΔH2, that is, the intersection of the high temperature peak ΔH2 in the DSC curve and the baseline on the high temperature side of the high temperature peak ΔH2.

[0178] After the straight line L2 is drawn, a straight line L3 is drawn which passes through the maximum point γ between the resin-specific peak ΔH1 and the high-temperature peak ΔH2 and is parallel to the vertical axis of the graph. The resin-specific peak ΔH1 and the high-temperature peak ΔH2 are divided by the straight line L3. The endothermic amount of the high-temperature peak ΔH2 can be calculated based on the area of ​​the portion constituting the high-temperature peak ΔH2 in the DSC curve, the straight line L2, and the portion surrounded by the straight line L3.

[0179] (Method for producing foamed particles)

[0180] The foamed particles can be produced, for example, by dispersing thermoplastic resin particles (hereinafter referred to as "resin particles") using a thermoplastic resin as a base resin in a dispersion medium, impregnating the resin particles with a foaming agent, and then releasing the resin particles containing the foaming agent together with the dispersion medium under low pressure. In addition, such a foaming method is sometimes referred to as a "direct foaming method".

[0181] Resin particles can be produced, for example, by a wire cutting method. In the wire cutting method, first, a thermoplastic resin as a base resin of a foaming layer and additives such as a bubble nucleating agent supplied as needed are supplied into an extruder, heated, and kneaded to form a resin melt kneaded product. Afterwards, the resin melt kneaded product is extruded from a small hole of a die head attached to the front end of the extruder to form an extrudate. After the extrudate is cooled, it is cut into a desired length, thereby obtaining a resin particle having a single-layer structure consisting of a core layer with a thermoplastic resin as a base resin.

[0182] In the case of foamed particles having a multilayer structure with a foaming layer and a weldability-improving layer, a coextrusion device having a core layer forming extruder, a weldability-improving layer forming extruder, and a coextrusion die connected to the two extruders is used to produce resin particles of the multilayer structure. In this case, in the core layer forming extruder, a first thermoplastic resin as a base material resin of the foaming layer and additives added as required are melt-kneaded to produce a core layer forming resin melt-kneaded product. In addition, in the weldability-improving layer forming extruder, a second thermoplastic resin as a base material resin of the weldability-improving layer and additives added as required are melt-kneaded to produce a weldability-improving layer forming resin melt-kneaded product.

[0183] These resin melt kneading products are coextruded and merged in a die head to form a composite of a multilayer structure consisting of a columnar core layer in a non-foamed state and a non-foamed weldability improving layer covering the outer surface of the core layer. The composite is extruded from a small hole in the die head to form an extrudate. After the extrudate is cooled, it is cut into a desired length to obtain resin particles of a multilayer structure. In addition, the manufacturing method of the resin particles is not limited to the above method, and a thermal cutting method, an underwater cutting method, etc. can also be used.

[0184] In the direct foaming method, the resin particles are foamed while roughly maintaining the shape of the resin particles. Therefore, the shape of the foamed particles obtained by the direct foaming method is roughly the shape of the resin particles after enlarging the shape. Therefore, in the case of wanting to obtain a cylindrical foamed particle with a through hole, the cylindrical resin particles with a through hole can be foamed. Such resin particles can be manufactured, for example, by using a die head with a small hole of a ring corresponding to the shape of the cut surface of the desired resin particle in the above-mentioned wire cutting method.

[0185] Similarly, when it is desired to obtain foamed particles having a cross-shaped cross section in the cut surface, it is sufficient to foam columnar resin particles having a cross-shaped cross section in the cut surface. Such resin particles can be produced, for example, by using a die head having a cross-shaped small hole corresponding to the shape of the cut surface of the desired resin particles in the above-mentioned wire cutting method.

[0186] When making resin particles, it is preferred to adopt a wire cutting method in which the cylindrical extrudate is cooled in water and then cut. In this case, the accuracy of the shape of the resin particles can be further improved, and the shape of the defective part in the finally obtained foamed particles can be more easily formed into a desired shape.

[0187] The particle size of the resin particles is preferably 0.1 mm to 3.0 mm, more preferably 0.3 mm to 1.5 mm. The ratio of the length to the outer diameter of the resin particles is preferably 0.5 to 5.0, more preferably 1.0 to 3.0.

[0188] In addition, the average mass of each resin particle is preferably 0.1 mg or more and 20 mg or less, more preferably 0.2 mg or more and 10 mg or less, further preferably 0.3 mg or more and 5 mg or less, and particularly preferably 0.4 mg or more and 2 mg or less. In addition, the average mass of each resin particle is the value obtained by dividing the mass of 200 randomly selected resin particles by the number of resin particles.

[0189] When the resin pellet has a core layer and a weldability improving layer, the mass ratio of the core layer to the weldability improving layer is preferably core layer: weldability improving layer = 99.5:0.5 to 80:20, more preferably 99:1 to 85:15, and further preferably 97:3 to 88:12.

[0190] In the foamed particles having through holes, by adjusting the average pore size dr of the through holes of the core layer in the resin particles, the average pore size d of the through holes of the foamed layer can be adjusted to the specific range. More specifically, by making the average pore size dr of the through holes of the resin particles be 0.10 mm or more and less than 0.25 mm, preferably 0.12 mm or more and less than 0.24 mm, more preferably 0.15 mm or more and less than 0.22 mm, it is possible to easily manufacture foamed particles having an average pore size d of the through holes of 0.1 mm or more and less than 1 mm. The average pore size dr of the through holes of the core layer of the resin particles can be adjusted, for example, by the pore size of the small hole of the die head used to form the through holes (i.e., the inner diameter of the die head).

[0191] In addition, by adjusting the particle size and average mass of the resin particles, the average outer diameter of the foamed particles can be adjusted to the above range. More specifically, by making the ratio dr / Dr of the average pore size dr of the through holes of the resin particles to the average outer diameter Dr be 0.4 or less, preferably 0.3 or less, more preferably 0.25 or less, and further preferably 0.2 or less, it is possible to easily manufacture foamed particles in which the ratio d / D of the average pore size d of the through holes of the foamed particles to the average outer diameter D is 0.4 or less. In addition, from the viewpoint of the manufacturing stability of the resin particles, the average pore size dr of the through holes of the resin particles is preferably 0.1 mm or more, and the ratio dr / Dr of the average pore size dr of the through holes of the resin particles to the average outer diameter Dr is preferably 0.1 or more.

[0192] The method for calculating the average pore diameter dr of the through holes of the resin particles and the average outer diameter Dr of the resin particles is the same as the method for calculating the average pore diameter d of the through holes of the foamed beads and the average outer diameter D of the foamed beads described above, except that resin particles are used instead of the foamed beads.

[0193] In addition, when a wire cutting method is used for cutting the extrudate, that is, a method in which a cylindrical extrudate extruded from a die is pulled while being cooled in water and then cut into an appropriate length, the particle size, length / outer diameter ratio and average mass of the resin particles can be adjusted by cutting by appropriately changing the extrusion speed, pulling speed, cutter speed, etc. during extrusion of the resin molten kneaded product.

[0194] After the resin particles are prepared as described above, the resin particles are dispersed in a dispersion medium. The operation of dispersing the resin particles in the dispersion medium may be performed in a sealed container used in the foaming step described later, or may be performed in a container different from the sealed container used in the foaming step. From the viewpoint of simplifying the manufacturing process, it is preferred to perform the dispersion process in a sealed container used in the foaming step.

[0195] As the dispersion medium, an aqueous dispersion medium with water as the main component is used. In the aqueous dispersion medium, in addition to water, a hydrophilic organic solvent such as ethylene glycol, glycerol, methanol, ethanol, etc. may also be included. The proportion of water in the aqueous dispersion medium is preferably 60% by mass or more, more preferably 70% by mass or more, and further preferably 80% by mass or more.

[0196] It is preferred to add a dispersant to the dispersion medium. By adding a dispersant to the dispersion medium, the welding of the resin particles heated in the container can be suppressed during the foaming process. The amount of the dispersant added is preferably 0.001 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the resin particles. As the dispersant, an organic dispersant or an inorganic dispersant can be used. From the perspective of ease of operation, particulate inorganic substances are preferably used as the dispersant. More specifically, as the dispersant, for example, clay minerals such as alumina, kaolin, mica, and clay, aluminum oxide, titanium oxide, basic magnesium carbonate, basic zinc carbonate, calcium carbonate, iron oxide, etc. can be used. These dispersants can be used alone or in combination of two or more dispersants. Among them, as the dispersant, clay minerals are preferably used. The clay mineral can be a natural clay mineral or a synthetic clay mineral.

[0197] When a dispersant is used, an anionic surfactant such as sodium dodecylbenzenesulfonate, sodium alkylbenzenesulfonate, sodium lauryl sulfate, sodium oleate, etc. is preferably used in combination as a dispersant. The amount of the dispersant added is preferably 0.001 parts by mass or more and 1 part by mass or less relative to 100 parts by mass of the resin particles.

[0198] After the resin particles are dispersed in the dispersion medium, the foaming agent is impregnated in the resin particles in a closed container. The foaming agent impregnated in the resin particles is preferably a physical foaming agent. As the physical foaming agent, inorganic physical foaming agents such as carbon dioxide, air, nitrogen, helium, argon, aliphatic hydrocarbons such as propane, butane, hexane, cyclopentane, cyclohexane, chlorofluoromethane, trifluoromethane, 1,1-difluoromethane, 1-chloro-1,1-dichloroethane, 1,2,2,2-tetrafluoroethane, chloromethane, chloroethane, halogenated hydrocarbons such as dichloromethane and organic physical foaming agents can be listed. These physical foaming agents can be used alone or in combination with two or more physical foaming agents. In addition, inorganic physical foaming agents and organic physical foaming agents can also be used in combination. From the perspective of environmental load and operability, it is preferred to use an inorganic physical foaming agent, and carbon dioxide is more preferred.

[0199] The amount of the foaming agent added is preferably 0.1 parts by mass or more and 30 parts by mass or less, and more preferably 0.5 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of the resin particles.

[0200] In the manufacturing process of the foamed beads, as a method for impregnating the resin particles with the foaming agent, a method can be adopted in which the foaming agent is supplied into a closed container, the pressure in the closed container is increased, and the foaming agent is impregnated into the resin particles in the dispersion medium. In this case, by heating the resin particles together with the dispersion medium, the impregnation of the foaming agent into the resin particles can be further promoted.

[0201] The pressure in the closed container during foaming is preferably more than 0.5MPa(G) with a gauge pressure. On the other hand, the pressure in the closed container is preferably less than 4.0MPa(G) with a gauge pressure. If within the above range, there is no hidden danger such as damage or explosion of the closed container, and the foaming particles can be safely manufactured.

[0202] Furthermore, when the dispersion medium is heated, the temperature during foaming can also be set to an appropriate range by raising the temperature of the dispersion medium at 1 to 5° C. / min.

[0203] After the impregnation of the foaming agent into the resin particles is completed, the contents of the sealed container are released into an environment with a lower pressure than the sealed container. As a result, the core layer of the resin particles foams to form a cell structure, and is cooled by the external air to stabilize the cell structure, thereby obtaining foamed particles.

[0204] When the base resin of the core layer is a crystalline thermoplastic resin, it is preferred to heat and foam in the following manner when the foaming agent is impregnated. That is, first, a primary holding step is performed at a temperature above (melting point of crystalline thermoplastic resin - 20°C) and below (melting end temperature of crystalline thermoplastic resin) for a sufficient time, preferably for about 10 to 60 minutes, and then, the temperature is adjusted from (melting point of crystalline thermoplastic resin - 15°C) to a temperature below (melting end temperature of crystalline thermoplastic resin + 10°C). Then, as needed, a secondary holding step is performed at this temperature for a further sufficient time, preferably for about 10 to 60 minutes. Afterwards, it is preferred to release the contents of the sealed container to the outside while the temperature in the sealed container is above (melting point of crystalline thermoplastic resin - 10°C) to foam the resin particles. The temperature in the sealed container during foaming is more preferably above (melting point of crystalline thermoplastic resin) and below (melting point of crystalline thermoplastic resin + 20°C). By heating and foaming the resin particles in this manner, secondary crystals are formed in the crystalline thermoplastic resin constituting the foamed layer, and foamed particles having excellent mechanical strength and excellent moldability can be easily obtained.

[0205] In the preparation of the molded body, the foamed particles obtained as above can also be used directly. In addition, the foamed particles obtained by the above-mentioned direct foaming method can be further foamed, and the foamed particles with increased stacking ratio can be used to prepare the molded body. In addition, when the resin particles are foamed in two stages like this, the foaming process of the first stage is called the primary foaming process, and the foamed particles obtained by the primary foaming process are called primary foamed particles. In addition, the foaming process of the second stage is called the secondary foaming process. The foamed particles obtained by the secondary foaming process are sometimes also called secondary foamed particles.

[0206] The method of increasing the stacking ratio of foamed particles by secondary foaming is, for example, as described below. First, as a primary foaming process, the resin particles are foamed by the above-mentioned direct foaming method to obtain primary foamed particles. Thereafter, internal pressure is applied to the primary foamed particles. More specifically, after the primary foamed particles are placed in a pressure-resistant container, the pressure-resistant container is pressurized using an inorganic gas such as air or carbon dioxide, so that the inorganic gas is impregnated into the foamed particles. Thus, the pressure inside the bubbles of the primary foamed particles is made to be above atmospheric pressure. Thereafter, the primary foamed particles taken out of the pressure-resistant container are heated using a heating medium such as steam or heated air in an environment with a lower pressure than the pressure inside the bubbles, thereby further foaming the primary foamed particles.

[0207] Example

[0208] Examples of the foamed beads, the foamed bead molded article, and the method for producing the same will be described.

[0209] (Thermoplastic resin)

[0210] Table 1 shows the properties of the polypropylene resin and polyamide resin used as thermoplastic resins in the manufacture of the foamed particles. The ethylene-propylene copolymer and ethylene-propylene-butene copolymer used in this example are both random copolymers. The density of PP1 shown in Table 1 is 900 kg / m 3 In addition, the density of PA1 shown in Table 1 is 1120 kg / m 3 In addition, PA1 is a product name manufactured by Ube Industries, Ltd.: UBE Nylon 6434B.

[0211] Table 1

[0212]

[0213] <Monomer Content of Polypropylene Resin>

[0214] The monomer content of the polypropylene resin (specifically, ethylene-propylene copolymer, ethylene-propylene-butene copolymer) is determined by a known method determined by using IR spectroscopy. Specifically, it is determined by the method described in the Handbook of Polymer Analysis (edited by the Polymer Analysis Research Symposium of the Japanese Society of Analytical Chemistry, published in January 1995, publisher: Kinokuniya Bookstore, page numbers and item names: 615-616 "II.2.32.3.4 Propylene / ethylene copolymer", 618-619 "II.2.32.3.5 Propylene / butene copolymer"), that is, a method of quantitatively determining the relationship between the value obtained by correcting the absorbance of ethylene and butene with a predetermined coefficient and the thickness of a film-like test piece.

[0215] More specifically, first, a polypropylene resin was heat-pressed in an environment of 180° C. to form a film, and a plurality of test pieces of different thicknesses were prepared. Next, the IR spectrum of each test piece was measured to read the 722 cm-1 wavelength derived from ethylene. -1 and 733cm -1 The absorbance at 722 , A 733 ) and 766cm from butene -1 The absorbance at 766 ). Next, for each test piece, the ethylene content in the polypropylene resin (unit: mass %) was calculated using the following formulas (6) to (8). The value obtained by arithmetic averaging the ethylene content obtained for each test piece was taken as the ethylene content in the polypropylene resin (unit: mass %).

[0216] (Kˊ 733 )c=1 / 0.96{(Kˊ 733 )a-0.268(Kˊ 722 )a}···(6)

[0217] (Kˊ 722 )c=1 / 0.96{(Kˊ 722 )a-0.150(Kˊ 733 )a}···(7)

[0218] Ethylene content = 0.575 {(K' 722 )c+(K′ 733 )c}···(8)

[0219] Among them, K′ in formulas (6) to (8) a is the apparent absorption coefficient (K′) at each wave number a =A / ρt), K′ c is the corrected absorption coefficient, A is the absorbance, and ρ is the density of the resin (unit: g / cm3 ), t is the thickness of the film-like test piece (unit: cm). In addition, the above formulas (6) to (8) can be applied to random copolymers.

[0220] The butene content (unit: mass %) in the polypropylene resin was calculated for each test piece using the following formula (9). The arithmetic average of the butene content obtained for each test piece was taken as the butene content (unit: mass %) in the polypropylene resin.

[0221] Butene content = 12.3 (A 766 / L)···(9)

[0222] In the formula (9), A is the absorbance, and L is the thickness of the film-like test piece (unit: mm).

[0223] <Flexural modulus of thermoplastic resin>

[0224] Thermoplastic resin was hot pressed at 230°C to produce a 4 mm sheet, from which a test piece of 80 mm in length × 10 mm in width × 4 mm in thickness was cut. The bending elastic modulus of the test piece was determined in accordance with JIS K7171: 2008. In addition, the radius R1 of the indenter and the radius R2 of the support were both 5 mm, the distance between the fulcrums was 64 mm, and the test speed was 2 mm / min.

[0225] <Melting Point of Thermoplastic Resin>

[0226] The melting point of the thermoplastic resin is determined based on JIS K7121:1987. Specifically, first, based on "(2) The case where the melting temperature is measured after a certain heat treatment" described in JIS K7121:1987, the state of the test piece composed of the thermoplastic resin is adjusted. The test piece after the state adjustment is heated from 30°C to 200°C at a heating rate of 10°C / min, thereby obtaining a DSC curve. Then, the top temperature of the melting peak that appears in the DSC curve is taken as the melting point. In addition, as a measuring device, a heat flux differential scanning calorimeter (manufactured by SII Nano Technology Co., Ltd., model: DSC7020) is used.

[0227] <Melt Mass Flow Rate of Thermoplastic Resin>

[0228] The melt mass flow rate (ie, MFR) of the thermoplastic resin is measured in accordance with JIS K7210-1:2014 under the conditions of a temperature of 230° C. and a load of 2.16 kg.

[0229] Next, the structure and production method of the foamed beads used in this example will be described.

[0230] (Foaming particles A)

[0231] As shown in Table 2, the foamed beads A have a multilayer structure, which includes a foamed layer 3 with PP1 (see Table 1) as a base resin, and a non-foamed weldability improving layer 4 with PP2 (see Table 1) as a base resin and covering the foamed layer 3. Fig. 9 as well as Fig.10 As shown, the foamed beads A have a cylindrical shape having a through hole 211 as a defect 21. The side circumference of the foamed beads A is covered with a fusion-improving layer 4, and the inside of the fusion-improving layer 4 is composed of a foamed layer 3.

[0232] When making foamed particles A, first, a coextrusion device having a core layer forming extruder, a weldability improving layer forming extruder, and a coextrusion die connected to the two extruders is used, and the extrudate extruded from the coextrusion device is cut by wire cutting to make multilayer resin particles with through holes. Specifically, PP1 and a bubble regulator shown in Table 1 are supplied to the core layer forming extruder, and melt-kneaded at a maximum setting temperature of 245°C in the extruder to obtain a core layer forming resin melt-kneaded product. In addition, zinc borate is used as a bubble regulator, and the amount of zinc borate added is set to 500 mass ppm relative to the polypropylene resin.

[0233] In addition, PP2 shown in Table 1 was melt-kneaded at a maximum set temperature of 245°C in an extruder for forming a weldability-improving layer to obtain a melt-kneaded resin for forming a weldability-improving layer. These melt-kneaded resins were co-extruded and merged in a die head, thereby forming a cylindrical composite consisting of a non-foamed cylindrical core layer and a non-foamed weldability-improving layer covering the outer surface of the cylindrical core layer. After the composite was extruded from a die head having a small hole for forming a through hole in the core layer, the extrudate was pulled while being cooled with cold water at a water temperature of 10°C, and cut into appropriate lengths using a pelletizer, thereby obtaining a multilayer resin pellet consisting of a cylindrical core layer having a through hole and a weldability-improving layer covering the core layer. The mass ratio of the core layer to the weldability-improving layer in the multilayer resin pellet was set to core layer: weldability-improving layer = 95:5 (i.e., the mass ratio of the weldability-improving layer was 5%). In addition, the mass of each multilayer resin pellet was about 1.5 mg.

[0234] Next, the multilayer resin particles were foamed by a direct foaming method to obtain foamed particles A. Specifically, 1 kg of the multilayer resin particles were put into a 5L sealed container together with 3L of water as a dispersion medium. Next, 0.3 parts by mass of a dispersant and 0.004 parts by mass of a dispersant were added to the sealed container relative to 100 parts by mass of the multilayer resin particles, and the multilayer resin particles were dispersed in the dispersion medium. Kaolin was used as the dispersant. In addition, a surfactant (sodium alkylbenzene sulfonate) was used as the dispersant.

[0235] Afterwards, carbon dioxide as a physical foaming agent is supplied into the sealed container while stirring the sealed container, so that the temperature in the container rises to 147.0°C. The pressure in the container at this time (i.e., impregnation pressure, carbon dioxide pressure) is 3.7MPa(G) in gauge pressure. After the temperature in the container reaches 147.0°C, the temperature is maintained for 15 minutes, thereby impregnating the multilayer resin particles with the physical foaming agent. After the impregnation of the physical foaming agent is completed, the sealed container is opened and the contents are released under atmospheric pressure, thereby foaming the multilayer resin particles. By the above, foamed particles A having a foaming layer formed by foaming a core layer and a non-foamed weldability improvement layer covering the foaming layer are obtained.

[0236] (Foaming particles B)

[0237] Foamed particles B are cylindrical in shape without through holes and without grooves on the side circumference. That is, foamed particles B do not have defects. When making foamed particles B, first, cylindrical resin particles having a core layer with PP1 as a base resin and a weldability improvement layer with PP2 as a base resin and without defects are made (see Table 2). The resin particles are foamed under the same conditions as foamed particles A, except that the temperature in the container is 150.1°C and the gauge pressure is 2.6MPa (G), thereby producing primary foamed particles. Next, the primary foamed particles are placed in a pressure-resistant container, and the pressure container is pressurized with air, thereby impregnating the air into the bubbles and increasing the internal pressure in the bubbles of the primary foamed particles. Thereafter, the primary foamed particles are taken out of the pressure-resistant container, steam is blown to the primary foamed particles, and they are heated at atmospheric pressure to obtain foamed particles B having the bulk density recorded in Table 2.

[0238] (Foaming particles C)

[0239] Foamed particles C have a cylindrical shape in which the average pore diameter of the through holes as defective parts is larger than that of foamed particles A. When foamed particles C are produced, first, a co-extrusion die having a small hole inner diameter of a die for forming through holes in a core layer different from the co-extrusion die used in the production of foamed particles A is used to produce cylindrical resin particles having a core layer with PP1 as a base resin and a weldability improving layer with PP2 as a base resin (see Table 2). The resin particles are foamed under the same conditions as those of foamed particles A, except that the temperature in the container is 146.4°C and the gauge pressure is 3.5 MPa (G), thereby obtaining foamed particles C.

[0240] (Foaming particles D)

[0241] As shown in Table 2, the foamed particles D have a single-layer structure consisting of a foamed layer 3 with PA1 (see Table 1) as a base resin. Figure 5 as well as Figure 6 As shown, the foamed beads D have a cylindrical shape having a through hole 211 as the defective portion 21 .

[0242] When making foamed particles D, first, an extrusion device equipped with an extruder for forming a core layer is used, and the extrudate extruded from the extruder is cut by a wire cutting method to make resin particles. Specifically, PA1 and a bubble adjuster shown in Table 1 are supplied to an extruder for forming a core layer, and melt-kneaded at a maximum setting temperature of 260°C in the extruder to obtain a core layer forming resin melt-kneaded product. After the melt-kneaded product is extruded from a die head equipped with a small hole for forming a through hole in the core layer, the extrudate is towed while being cooled with cold water at a water temperature of 10°C, and a granulator is used to cut it into an appropriate length, thereby obtaining a resin particle consisting of a cylindrical core layer with a through hole. In addition, talc is used as a bubble adjuster, and the amount of talc added is set to 3000 mass ppm relative to the polyamide resin. In addition, the mass of each resin particle is about 1.5 mg.

[0243] Next, the resin particles were foamed by a direct foaming method to obtain foamed particles D. Specifically, 1 kg of the resin particles were put into a 5 L sealed container together with 3 L of water as a dispersion medium. Next, 0.3 parts by mass of a dispersant and 0.004 parts by mass of a dispersant were added to 100 parts by mass of the resin particles in the sealed container to disperse the resin particles in the dispersion medium. Kaolin was used as the dispersant. In addition, a surfactant (sodium alkylbenzene sulfonate) was used as the dispersant.

[0244] Afterwards, carbon dioxide as a physical foaming agent is supplied into the sealed container while stirring the sealed container, so that the temperature in the container rises to 131.0°C. The pressure in the container at this time (i.e., impregnation pressure, carbon dioxide pressure) is 4.0MPa(G) in gauge pressure. After the temperature in the container reaches 131.0°C, the temperature is maintained for 15 minutes, thereby impregnating the physical foaming agent into the resin particles. After the impregnation of the physical foaming agent is completed, the sealed container is opened and the contents are released under atmospheric pressure, thereby foaming the resin particles. Thus, foamed particles D having a foaming layer formed by foaming the core layer are obtained.

[0245] (Foaming particles E)

[0246] The foamed particles E are cylindrical in shape without through holes and without grooves on the side circumference. That is, the foamed particles E do not have defects. The method for manufacturing the foamed particles E is the same as the method for manufacturing the foamed particles D, except that the defects are not provided during the production process of the resin particles.

[0247] Next, a molded article was produced by the following method using the above-mentioned expanded beads A to E.

[0248] (Examples 1 to 3 and Comparative Examples 1 to 4)

[0249] First, the foamed particles shown in Tables 3 and 4 are dried at 23°C for 24 hours and then immersed in air to increase the internal pressure, i.e., the pressure inside the bubbles, to the value shown in the "Particle Internal Pressure" column of Tables 3 and 4. In addition, in Comparative Example 3, since the foamed particles are not given internal pressure, the symbol "-" is recorded in the "Particle Internal Pressure" column. The internal pressure of the foamed particles is a value measured as follows. The mass Q (unit: g) of the foamed particle group in a state of increased internal pressure just before being filled into the forming mold and the mass U (unit: g) of the foamed particle group after 48 hours are measured, and the difference between Q and U is taken as the amount of air added W (unit: g). Using these values, the internal pressure of the foamed particles (unit: MPa(G)) is calculated based on the following formula (10).

[0250] P=(W / M)×R×T / V···(10)

[0251] Wherein, M in the formula (10) is the molecular weight of air, R is the gas constant, T is the absolute temperature, and V is the volume obtained by subtracting the volume of the base resin occupied by the foamed particle group from the apparent volume of the foamed particle group (unit: L). In this example, M=28.8 (g / mol), R=0.0083 (MPa·L / (K·mol)), and T=296 (K).

[0252] Next, the mold is filled with foamed particles by the crack filling method (crack filling step). Figure 1 to Figure 4As shown, the forming mold 1 used in this example has a fixed mold 11 and a movable mold 13 that is configured to be reciprocating in one direction relative to the fixed mold 11. In addition, the forming mold 1 is configured to form a forming cavity 12 between the fixed mold 11 and the movable mold 13. The forming cavity 12 in the forming mold 1 of this example is configured to be able to form a bottomed box-shaped forming body. The outer dimensions of the forming body formed by the forming mold 1 of this example are 300 mm in length × 200 mm in width × 60 mm in thickness. In addition, an opening portion with inner dimensions of 200 mm in length × 150 mm in width × 45 mm in depth is provided in the center of the surface of the forming body that is 300 mm in length × 200 mm in width. In the forming mold 1, the thickness direction of the forming body corresponds to the opening and closing direction of the forming mold, the longitudinal direction corresponds to the height direction of the forming cavity, and the lateral direction corresponds to a direction orthogonal to both the opening and closing direction of the forming mold and the height direction of the forming cavity. The average length L in the opening and closing direction of the forming mold is expressed by the following formula (1): A As shown in Table 3 and Table 4.

[0253] L A =V / S···(1)

[0254] Wherein, V in the formula (1) is the volume of the molding cavity when the molding die is completely closed (unit: mm 3 ), S is the projection area of ​​the forming cavity when projecting the forming cavity in the opening and closing direction of the forming mold (unit: mm 2 ).

[0255] In addition, the molding cavity 12 has a length in the opening and closing direction when the molding die 1 is completely closed, which is smaller than the average length L. A The length of the long first portion 121 in the opening and closing direction is greater than the average length L A The second short part 122. Figure 1 to Figure 4 As shown in Table 3, the first portion 121 of the molding cavity 12 in this example corresponds to the side wall of the molding body, and the second portion 122 corresponds to the bottom wall of the molding body. Tables 3 and 4 show the maximum value L1 of the length of the first portion of the molding cavity in the opening and closing direction measured when the molding die 1 is completely closed. max and the minimum length L2 of the second portion in the opening and closing direction min .

[0256] In the crack filling process, Figure 1 As shown in FIG. 1 , the foamed particles 2 are supplied from the hopper 14 to the forming mold 1 in a state where the forming mold is opened so that the size of the crack gap δ, that is, the distance in the opening and closing direction from the fixed mold 11 to the movable mold 13 when the foamed particles are filled, is the value shown in Table 3 and Table 4. Figure 2As shown, after the filling of the foamed particles 2 into the molding cavity 12 is completed in a state where a gap is formed between the fixed mold 11 and the movable mold 13, as shown in FIG. Figure 3 As shown, the forming die 1 is completely closed to mechanically compress the foamed beads 2. The minimum value P1 of the compression rate of the first part at this time is min And the maximum compression ratio of the second part P2 max The values ​​are shown in Table 3 and Table 4. In addition, the minimum value P1 of the compression ratio of the first part min And the maximum compression ratio of the second part P2 max It is calculated by the following formula (2) and formula (3).

[0257] P1 min =(δ / L1 max )×100···(2)

[0258] P2 max =(δ / L2 min )×100···(3)

[0259] After the forming mold is completely closed, a venting process is performed by supplying steam as a heating medium from both sides of the forming mold for 5 seconds for preheating. After that, steam is supplied from one side of the forming mold for one-side heating until a pressure of 0.08MPa(G) lower than the forming pressure during formal heating shown in Tables 3 and 4 is reached. Next, steam is supplied from the other side of the forming mold for one-side heating until a pressure of 0.04MPa(G) lower than the forming pressure during formal heating is reached. After that, steam is supplied from both sides of the forming mold for formal heating until the forming pressure shown in Tables 3 and 4 is reached. After the formal heating is completed, the pressure in the forming mold is released, and the formed body is cooled in the forming mold until the surface pressure of the formed body based on the foaming force reaches 0.04MPa(G). After that, the formed body is removed from the forming mold. The demolded formed body is left to stand in an oven at 80°C for 12 hours for a curing process. After the curing step, the molded body was allowed to stand for 24 hours under the conditions of a relative humidity of 50%, 23° C., and 1 atm to condition the molded body. The molded body obtained in this way was subjected to the evaluation of the molded body described below.

[0260] (Example 4)

[0261] In Example 4, a molded body was produced by the same method as in Example 1, except that a mold 1 having a different shape of the mold cavity 12 was used. The mold cavity 12 of the mold 1 used in this example was a bottomed box-shaped body having outer dimensions of 500 mm in length × 300 mm in width × 100 mm in thickness, and was configured to be able to mold a molded body having an opening portion having inner dimensions of 375 mm in length × 200 mm in width × 70 mm in depth in the center of a surface of 500 mm in length × 300 mm in width.

[0262] (Example 5, Comparative Example 5)

[0263] In Example 5 and Comparative Example 5, as shown in Tables 3 and 4, molded bodies were produced by the same method as in Example 1 except that polyamide resin foamed particles were used.

[0264] The characteristics of the foamed beads and the molded bodies in the embodiments and comparative examples are shown in Tables 2 to 4. The evaluation methods of the characteristics shown in Tables 2 to 4 are as follows. In addition, in the molded body of Comparative Example 4, the foamed beads in the thin-walled portion (bottom wall) are not fused at all, and a molded body of the desired shape cannot be obtained, so no evaluation other than the fusion rate is performed. Therefore, in the column other than the fusion rate in Comparative Example 4, a symbol "-" indicating that no evaluation was performed is recorded. In addition, in Comparative Examples 1 to 5, in the evaluation of the molded body using the curing process, the surface properties and / or fusion properties are poor, and a good molded body cannot be obtained, so the dimensional stability evaluation when the curing process is omitted is not performed. Therefore, in the dimensional stability column of Comparative Examples 1 to 5, a symbol "-" indicating that no evaluation was performed is recorded.

[0265] (Evaluation of Foamed Particles)

[0266] For the measurement and evaluation of physical properties of the expanded beads, the expanded beads were conditioned by standing for 24 hours under the conditions of a relative humidity of 50%, 23° C., and 1 atm.

[0267] <Bulk Density>

[0268] The foamed beads after the state adjustment are filled into the graduated cylinder in a natural stacking manner, and the stacking volume (unit: L) of the foamed beads group is read from the scale of the graduated cylinder. Then, the mass of the foamed beads group in the graduated cylinder (unit: g) is divided by the above-mentioned stacking volume, and the unit is further converted to calculate the bulk density of the foamed beads (unit: kg / m 3 ).

[0269] <Apparent density>

[0270] After measuring the mass of the foamed particle group after the state adjustment, use a metal mesh to sink it into a measuring cylinder filled with ethanol at a temperature of 23°C. Then, taking into account the volume of the metal mesh, the volume of the foamed particle group read out according to the amount of water level rise is measured. After dividing the mass of the foamed particle group obtained in this way (unit: g) by the volume (unit: L), the units are converted to calculate the apparent density of the foamed particles (unit: kg / m 3 ). In addition, the column "Apparent density / bulk density" in Table 2 shows the ratio of the apparent density to the bulk density obtained by the above method.

[0271] Average diameter of through holes d

[0272] The average pore size d of the through holes of the foamed particles is calculated as follows. First, the foamed particle group is allowed to stand for more than 24 hours in an environment of relative humidity of 50%, temperature of 23°C, and air pressure of 1 atm to adjust the state of the foamed particles. For 100 foamed particles randomly selected from the foamed particle group after state adjustment, they are cut at the center of the axial direction with a plane perpendicular to the axial direction, thereby exposing the cut surface. Take a photo of the cut surface of each foamed particle, and calculate the cross-sectional area (opening area) of the through hole portion in the cross-sectional photo. Calculate the diameter of an imaginary circle with the same area as the cross-sectional area, and take the value obtained by arithmetic averaging them as the average pore size d (unit: mm) of the through holes of the foamed particles.

[0273] Average outer diameter D of foamed particles

[0274] The average outer diameter of the foamed particles is calculated as follows. First, the foamed particle group is allowed to stand for more than 24 hours in an environment of relative humidity of 50%, temperature of 23°C, and air pressure of 1atm to adjust the state of the foamed particles. For 100 foamed particles randomly selected from the foamed particle group after state adjustment, they are cut at the center of the axial direction with a plane perpendicular to the axial direction, thereby exposing the cut surface. A photograph of the cut surface of each foamed particle is taken to calculate the cross-sectional area of ​​the foamed particles (including the opening of the through hole). Calculate the diameter of an imaginary circle with the same area as the cross-sectional area, and take the value obtained by arithmetic averaging them as the average outer diameter D (unit: mm) of the foamed particles. In addition, the value of the ratio d / D of the average pore size d of the through holes of the foamed particles to the average outer diameter D is also recorded in Table 2.

[0275] Average wall thickness of foamed particles t

[0276] The average wall thickness t (unit: mm) of the foamed beads was calculated using the average outer diameter D (unit: mm) of the foamed beads and the average pore diameter d (unit: mm) of the through-holes based on the following formula (5). In addition, Table 2 also lists the value of the ratio t / D of the average wall thickness t of the foamed beads to the average outer diameter D.

[0277] t=(Dd) / 2···(5)

[0278] <Total cross-sectional area Ct of defects, average cross-sectional area Ca of each defect>

[0279] 100 foamed beads are randomly selected from the foamed bead group after the state adjustment, and these foamed beads are cut at the center of the axial direction with a plane perpendicular to the axial direction to expose the cut surface. Then, a photograph of the cut surface of the foamed beads is taken, and the image is analyzed to measure the cross-sectional area C of the through hole of each foamed bead (refer to Fig.10 ).

[0280] The above operation is performed on 100 foamed particles, and the arithmetic mean of the cross-sectional areas of the through holes obtained is taken as the total cross-sectional area Ct of the defects. In addition, in the foamed particles A to C, since each foamed particle is provided with a through hole, the average cross-sectional area Ca of each defect is equal to the total cross-sectional area Ct of the defects. Table 2 records the ratio Ct / A of the total cross-sectional area Ct of the defects in the cut surface to the average cross-sectional area A of the foamed particles and the ratio Ca / A of the average cross-sectional area Ca of each defect to the average cross-sectional area A of the foamed particles.

[0281] In addition, the calculation method of the average cross-sectional area A of the above-mentioned foamed particles is as follows. First, the foamed particles are cut at the center of their axial direction with a plane perpendicular to the axial direction to expose the cut surface. The cross-sectional area of ​​the foamed particles 2 in the cut surface is measured. The cross-sectional area of ​​the foamed particles 2 is the sum of the cross-sectional area of ​​the foamed layer 3 and the cross-sectional area of ​​the weldability improvement layer 4 in the cut surface. The measurement of the cross-sectional area of ​​the foamed particles 2 in the cut surface is performed by taking a photograph of the cut surface of the foamed particles and performing image analysis. The cross-sectional area of ​​the defective portion is not included in the cross-sectional area of ​​the foamed particles. The above operation is performed on 100 foamed particles, and the arithmetic mean of the cross-sectional areas of the obtained foamed particles is taken as the average cross-sectional area A of the foamed particles.

[0282] <Water cooling time>

[0283] When the expanded beads were in-mold molded, the time from the time when the main heating was completed to the time when the surface pressure of the molded body due to the foaming force reached 0.04 MPa (G) was measured and this time was taken as the water cooling time.

[0284] (Evaluation of Molded Body)

[0285] <Average Density of Molded Body>

[0286] The average density of the molded body (unit: kg / m 3 ).

[0287] <Density of Side Wall and Bottom Wall>

[0288] First, test pieces are cut from the side wall and bottom wall of the molded body in a manner that does not include the surface surface, that is, the surface that contacts the mold during in-mold molding. In addition, the side wall of the molded body is a thick portion corresponding to the first portion of the molding cavity, and is a portion where the compression rate of the foamed particles in the crack filling process is relatively low. In addition, the bottom wall of the molded body is a thin portion corresponding to the second portion of the molding cavity, and is a portion where the compression rate of the foamed particles in the crack filling process is relatively high.

[0289] The density of the side wall and the bottom wall (unit: kg / m) was calculated by dividing the mass of the test pieces (unit: g) by the volume (unit: L) obtained from the outer dimensions of the test pieces and converting the units. 3 ).

[0290] <Welding rate of side wall and bottom wall>

[0291] Rectangular test pieces are cut out from the side walls and bottom walls of the molded body in a manner that does not include the surface surface. These test pieces are broken by bending them in a manner that is roughly equally divided in the long side direction. Afterwards, the fracture surface of the test piece is observed, and the number of foamed particles whose foamed particles themselves are broken (material damage) and the number of foamed particles peeled off between the interfaces of the foamed particles are measured by visual inspection. Then, the ratio of the number of foamed particles with material damage to the total number of foamed particles present on the fracture surface is calculated, and the value of this ratio expressed as a percentage is used as the welding rate of the side walls and the bottom wall (unit: %).

[0292] <Tensile Strength of Side Wall and Bottom Wall>

[0293] The tensile strength of the side wall and the bottom wall is measured in accordance with JIS K6767:1999. Specifically, first, a vertical slicer is used to cut out rectangular slices of 120 mm × 25 mm × 10 mm thick from the side wall and the bottom wall in the short side direction of the formed body, with all the faces as the cutting faces and the thickness direction of the slices being the thickness direction of the formed body. Dumbbell-shaped No. 1 test pieces are made from these slices using a dumbbell-shaped die. A tensile test is carried out using the obtained test piece at a tensile speed of 500 mm / min to prepare a load-displacement curve. The maximum tensile stress in the load-displacement curve is taken as the tensile strength of the side wall and the bottom wall. In addition, the tensile strength is an indicator of the toughness of the formed body.

[0294] <50% compressive stress of side wall>

[0295] A test piece having a rectangular shape of 50 mm × 50 mm × 25 mm thick was cut from the side wall in the short side direction of the molded body in such a way that the surface surface is not included and the thickness direction of the test piece is the thickness direction of the molded body. Based on JIS K6767:1999, a compression test was performed at a compression speed of 10 mm / min, thereby obtaining the 50% compressive stress (unit: kPa) of the side wall of the molded body. In addition, the 50% compressive stress is an indicator of the rigidity of the molded body.

[0296] <Porosity of Side Wall and Bottom Wall>

[0297] A test piece having a rectangular shape of 20 mm × 100 mm × 20 mm thick is cut out from the side walls and bottom walls in the short side direction of the formed body in such a way that the thickness direction of the test piece is the thickness direction of the formed body. The test piece is sunk into a measuring cylinder filled with ethanol, and the true volume Vc (unit: L) of the test piece is calculated from the rising amount of the liquid level of ethanol. In addition, the apparent volume Vd (unit: L) of the test piece is calculated from the outer dimensions of the test piece. Using the true volume Vc and apparent volume Vd of the test piece obtained as above, the porosity (unit: %) of the side wall and the bottom wall is calculated based on the following formula (4).

[0298] Void ratio = [(Vd-Vc) / Vd] × 100 (4)

[0299] <Surface Properties>

[0300] The appearance of the molded body is evaluated based on the results obtained by visually observing the surface of the inner side of the bottom wall of the molded body. In the "Appearance" column in Tables 3 and 4, when there are few gaps between the foamed particles on the surface of the molded body and the unevenness caused by defects such as through holes is not obvious, it is recorded as "A", when unevenness caused by defects such as gaps between particles and / or through holes is slightly confirmed on the surface of the molded body, it is recorded as "B", and when unevenness caused by defects such as gaps between particles and / or through holes is significantly confirmed on the surface of the molded body, it is recorded as "C".

[0301] <Shape stability when curing process is omitted>

[0302] After removing the molded body from the forming mold, the molded body without the curing process is used to evaluate the shape stability. Specifically, the molded body after demolding is left to stand for 24 hours under the conditions of relative humidity of 50%, 23°C, and 1atm, thereby adjusting the state of the molded body. Using the molded body after state adjustment, when observing the molded body from the top view in the thickness direction, the thickness of the bottom wall at four locations 10 mm inward from each vertex of the inner surface of the bottom wall to the center direction and the thickness of the bottom wall in the central part are measured respectively. Next, the ratio of the thickness of the thinnest part to the thickness of the thickest part among the measured parts is calculated (unit: %). In the "Shape Stability" column of Tables 3 and 4, when the thickness ratio is 95% or more, it is recorded as "good", and when it is less than 95%, it is recorded as "poor".

[0303] Table 2

[0304]

[0305] Table 3

[0306]

[0307] Table 4

[0308]

[0309] As shown in Table 3, in Examples 1 to 5, the difference in compression ratio P2 max -P1 min After the shape of the molding cavity and the size δ of the crack gap are set in the manner within the specific range and the crack is filled with foamed particles, in-mold molding is performed. The foamed particles used in Examples 1 to 5 have the specific shape described above. Therefore, in Examples 1 to 5, the water cooling time can be shortened. In addition, the molded bodies of Examples 1 to 5 have excellent appearance, high welding rates of thick-walled parts and thin-walled parts, and excellent toughness and rigidity.

[0310] On the other hand, as shown in Table 2, the foamed particles B used in Comparative Examples 1 and 2 are conventional polypropylene resin foamed particles without defects. In addition, the foamed particles E used in Comparative Example 5 are conventional polyamide resin foamed particles without defects. When such foamed particles B and foamed particles E are subjected to crack filling and then molded, as shown in Table 4, the water cooling time becomes longer. In addition, the foamed particles on the bottom wall with a high compression rate during the crack filling process are not sufficiently welded to each other, and the toughness of the bottom wall is reduced. In particular, when the difference in compression rate P2 is max -P1 min In Comparative Example 2, which is relatively high, the water cooling time is significantly long and the welding rate is significantly low.

[0311] As shown in Table 2, in the expanded beads C used in Comparative Example 3, the ratio Ca / A of the average cross-sectional area Ca of each defect to the average cross-sectional area A of the expanded beads and the ratio Ct / A of the total cross-sectional area Ct of the defects to the average cross-sectional area A of the expanded beads were too large. If in-mold molding is performed after the crack filling of such expanded beads C, the appearance of the molded body is poor and the mechanical properties such as rigidity and toughness are reduced due to the insufficient secondary foaming of the expanded beads in the side wall with a low compression rate during the crack filling process and the large defects.

[0312] Comparative Example 4 is an example in which the same foamed particles A as in Examples 1 to 4 are used, but the size of the crack gap δ is larger than that in Examples 1 to 4. As shown in Table 4, under the molding conditions of Comparative Example 4, the minimum value P1 of the compression ratio of the first part is min The maximum compression ratio of the second part P2 max Difference P2 max -P1 min As a result, the foamed particles cannot be welded to each other in the second part.

[0313] The specific method of manufacturing the thermoplastic resin foamed particle molded body involved in the present invention is described above based on the embodiments, but the specific method of manufacturing the thermoplastic resin foamed particle molded body involved in the present invention is not limited to the embodiment, and the structure can be appropriately changed within the scope of not damaging the main purpose of the present invention.

Claims

1. A method for producing a thermoplastic resin foamed particle molded body, wherein: The method for producing the thermoplastic resin foamed particle molded body comprises: a crack filling step of filling the molding cavity of the molding die with the crack gap opened with thermoplastic resin foamed particles having a foam layer, and then completely closing the molding die; and In the in-mold forming process, after the crack filling process is completed, a heating medium is supplied into the forming cavity to fuse the foamed particles to each other, thereby producing a foamed foam with a thickness of 10 kg / m 3 Above and 150kg / m 3 A thermoplastic resin foamed particle molded body having a molded body density of The foamed layer is composed of a crystalline thermoplastic resin. When the forming mold is completely closed, the forming cavity has a first portion and a second portion, and the length of the first portion in the opening and closing direction of the forming mold is greater than the average length L represented by the following formula (1): A The length of the second portion in the opening and closing direction of the forming mold is longer than the average length L A short, The minimum value P1 of the compression rate of the first portion represented by the following formula (2) in the crack filling step is: min The maximum value P2 of the compression rate of the second part expressed by the following equation (3) max Difference P2 max -P1 min is 5% or more and 100% or less, The average length L of the forming cavity in the opening and closing direction A More than 10mm, The foamed bead has a columnar shape and has one or more defective parts selected from the group consisting of a through hole that axially penetrates the inside of the foamed bead and a groove that extends axially on the side circumference of the foamed bead. In a cross section obtained by cutting the foamed beads at the center of the axial direction with a plane perpendicular to the axial direction, a ratio Ca / A of an average cross-sectional area Ca of each defect to an average cross-sectional area A of the foamed beads is greater than or equal to 0.01 and less than or equal to 0.20, and a ratio Ct / A of a total cross-sectional area Ct of the defects to an average cross-sectional area A of the foamed beads is greater than or equal to 0.02 and less than or equal to 0.20, L A =V / S···(1) P1 min =(δ / L1 max )×100%···(2) P2 max =(δ / L2 min )×100%···(3) Wherein, V in the formula (1) is the volume of the forming cavity when the forming mold is completely closed, and the unit is mm 3 , S is the projection area of ​​the forming cavity when projecting the forming cavity in the opening and closing direction of the forming mold, in mm 2 , δ in the formula (2) and formula (3) is the size of the gap in the gap filling process, in mm, and L1 in the formula (2) max is the maximum value of the length of the first portion in the opening and closing direction measured when the forming mold is completely closed, in mm. L2 in the formula (3) min It is the minimum value of the length of the second portion in the opening and closing direction measured when the forming mold is completely closed, and the unit is mm.

2. The method for producing a thermoplastic resin foamed particle molded article according to claim 1, wherein: A ratio of the apparent density of the foamed particles to the bulk density of the foamed particles is greater than 1.6 and less than 2.

0.

3. The method for producing a thermoplastic resin foamed particle molded body according to claim 1 or 2, wherein: The maximum value P2 of the compression rate of the second portion in the crack filling step max It is 25% or more and 150% or less.

4. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The maximum value L1 of the length of the first portion in the opening and closing direction of the forming die max More than 55mm.

5. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The thermoplastic resin foamed particle molded body obtained by the production method has a fusion rate of 70% or more at a portion corresponding to the first portion.

6. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The thermoplastic resin foamed particle molded article obtained by the above production method has a void ratio of 4% to 12%.

7. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The foamed beads have one or more through holes as the defective portions.

8. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The foamed beads include a foamed layer and a weldability improving layer covering the foamed layer. The base resin of the foamed layer is a first crystalline thermoplastic resin, and the base resin of the weldability improving layer is a second thermoplastic resin.

9. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The crystalline thermoplastic resin constituting the foamed layer is a polyolefin-based resin.

10. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The crystalline thermoplastic resin constituting the foamed layer is an ethylene-propylene random copolymer having an ethylene component content of 0.5% by mass or more and 3.5% by mass or less.

11. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The bulk density of the foamed particles is 10 kg / m 3 Above and 50kg / m 3 the following.

Citation Information

Patent Citations

  • Method for manufacturing in-mold molded foam polypropylene particle

    JP2003201361A

  • Polyolefin-based resin foam particles, polyolefin-based resin foam particle molded body, and production method for polyolefin-based resin foam particles

    WO2020189389A1

  • Apparatus for producing foamed moldings, and methos for producing laminated foamed moldings and foamed molding produced thereby

    CN1460057A

  • Process and apparatus for producing foamed styrenic polymers

    EP1995273A2